Calcium dysregulation in neurovascular function in Alzheimer’s disease: mechanisms, therapeutic targets - Yvan Hanscom-Trofy; Andrew Gregory; Gilbert C. Morgan; Hongwei Yu; Rui Dong; Fan Fan (GeroScience, 2026)

Vancomycin-resistant Enterococcus faecium: a national wide genomic snapshot in Switzerland - Dominique S. Blanc; Florian Mauffrey; Andrea C. Büchler; Danielle Vuichard-Gysin; Vanja Piezzi; Céline Gardiol; Marc Garcia; Trestan Pillonel; Laurent Poirel; Patrice Nordmann; Pascal Schlaepfer; Claudio Neidhöfer; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Heart rate and sub-blubber temperature in harbour seals (Phoca vitulina) measured during the moult and post-moult using implantable loggers - W. D. Paterson; L. L. Chaise; S. E. Moss; R. Milne; C. Gilbert; J. I. Currie; D. Thompson; D. J. McCafferty (Journal of Comparative Physiology B, 2026)
The moult represents an important seasonal change in the physiology of phocid seals. However, physiological measurements are challenging due to the impracticalities of instrumenting moulting animals. The aim of this study was (i) to assess the feasibility of a long-term deployment of fully implantable loggers to measure heart rate (HR) and sub-blubber temperature (T b ) in harbour seals ( Phoca vitulina ) and (ii) to compare HR and T b during moult and post-moult periods. Loggers were surgically implanted on an adult and sub-adult harbour seal in captivity. Animals healed quickly from surgery and loggers provided 65 days of continuous data before removal of the device. Results showed that in the adult when hauled out and in the water HR was lower during the moult compared with the post-moult. For the sub-adult, HR while in the water was also higher during the post-moult, however, when hauled out there was no difference in HR between the moult and post-moult periods. When hauled out, T b was greater for both animals during the moult compared with the post-moult. During haulout events, T b increased over time in both periods and T b in both animals was lower during post moult compared to the moult period. In the sub-adult, T b decreased with time in the water during the moult but showed little change during the post-moult period, whereas no temporal change was evident in the adult during either period. This study demonstrated that fully implantable loggers are a useful research tool allowing measurement of physiological parameters that are otherwise difficult to measure in pinnipeds. Physiological measurements suggested that the requirement to maintain higher skin temperature for hair growth during the moult was offset by lower metabolism to save energy in water, and on land in the case of adults. However, a decrease in body temperature with time in water in the sub-adult indicated that a smaller body size and less well-developed blubber layer is not as effective in reducing heat loss compared to adults. Future physio-logging on pinnipeds throughout their annual lifecycle may therefore benefit from similar techniques used to implant loggers.

The Matador Bug and Several Related Leaf-footed Bugs (Hemiptera: Coreidae) Accumulate Cyanogens From their Host Plants - Colin R. Morrison; Brian E. Sedio; Lawrence E. Gilbert; Justin C. Havird; Ummat Somjee (Journal of Chemical Ecology, 2026)

Comparison of Leptosira concentrations in two rivers within contrasting catchments in a leptospirosis hotspot - R. Thibeaux; P. Genthon; R. Govan; N. Selmaoui-Folcher; A. Peltier; M. Kainiu; M.-E. Soupé-Gilbert; O. Yu; C. Tramier; K. Wijesurriya; C. Goarant (Journal of Contaminant Hydrology, 2026)

Ecological niche overlap in a warming boreal river: a case study of brook trout (Salvelinus fontinalis) and fallfish (Semotilus corporalis) - Aglaé H. Lambert; Gilbert Cabana; Eva C. Enders (Environmental Biology of Fishes, 2026)

Age of the Acraman impact ejecta layer in the adelaide superbasin and Implications on clay-mineral provenance from the Rb–Sr systematics of middle Ediacaran shales - Alan S. Collins; Morgan L. Blades; Darwinaji Subarkah; Holly Cooke; Lesley Edwards; Chelsea Forbister; Jake Jolly; Jarred C. Lloyd; Sarah E. Gilbert; Stefan Löhr; Juraj Farkaš; Victor Gostin (Precambrian Research, 2026)

Cumulative effects analysis to inform public land management in the United States: key characteristics and legal challenges - Tait K. Rutherford; Tim O. Hammond; Alison C. Foster; Megan A. Gilbert; Travis S. Haby; Richard J. Lehrter; Jennifer K. Meineke; Ella M. Samuel; Sarah K. Carter (Environmental Impact Assessment Review, 2026)

PTUPB improves cognitive function in Alzheimer’s disease associated with enhancing cerebral vascular myogenic response and attenuating vascular remodeling - Gilbert C. Morgan; Andrew Gregory; Chengyun Tang; Sung Hee Hwang; Jane J. Border; Jing Xu; Yedan Liu; Shan Bai; Tae Jin Lee; Cameron Cantwell; David Bunn; Karen M. Wagner; et al. (GeroScience, 2026)

The European Biophysics Journal Prizes 2025: Recognising biophysical science at sub-cellular, cellular and tissue levels of organisation - Robert J. C. Gilbert (European Biophysics Journal, 2026)
The European Biophysics Journal Prizes for 2025, awarded at the European Biophysical Societies Association (EBSA) Congress in Rome last July, recognised three of the outstanding papers published by the Journal in 2022 and 2023. In making these awards, the Journal and EBSA again sought to recognise publications which were already proving their impact. The studies recognised are diverse and highlight the vitality of biophysical science in the 2020s. They concern studies of (i) synaptic vesicles undergoing glutamate uptake, (ii) red blood cells under pressure and the effects of mechanically triggered calcium influx, and (iii) how ciliary beating, the resulting wave effects and downstream transport processes interrelate in trachea. As such these Prizes recognise excellent biophysical science at sub-cellular, cellular and tissue levels of organisation.

Heterogeneity, Productivity, and Migration Drive Continental Evenness Patterns of Bird Assemblages - Neil A. Gilbert; Natalie Queally; Jacob C. Cooper; Harold N. Eyster; Peter J. Williams (Global Ecology and Biogeography, 2026)
Aim Evenness quantifies similarities in abundances among species in an assemblage and may influence processes such as species coexistence and the supply of ecosystem services. Previous work has failed to identify generalised patterns of how productivity and habitat heterogeneity influence evenness and moreover has not considered seasonal variation in evenness arising from migration. Therefore, our goal was to quantify the interplay of productivity, habitat heterogeneity, and migration on evenness patterns of bird assemblages. Location Contiguous United States. Time Period Contemporary. Group Birds (613 species). Methods Using relative abundance maps from eBird, we computed evenness of bird assemblages for 27 × 27 km grid cells at weekly temporal resolution. We used generalized linear mixed‐effects models to evaluate the influences of productivity (normalized difference vegetation index), habitat heterogeneity (Shannon diversity of land cover), and the dominance of migratory species on evenness. Results Productivity and heterogeneity interacted to influence evenness such that there was a positive productivity–evenness relationship in high‐heterogeneity landscapes but no relationship in low‐heterogeneity landscapes. Evenness was highest during the pre‐breeding and breeding seasons when migratory taxa were present, but a high dominance of migrants reduced evenness and generally dampened evenness–productivity relationships. Main Conclusions Evenness increased with productivity in high‐heterogeneity—but not low‐heterogeneity—landscapes, indicating that hypotheses relating to energy availability and niche partitioning should be considered jointly. Higher evenness during the growing season likely reflects the presence of low‐abundance migrant taxa, whereas the negative effects of migrant dominance on evenness are likely driven by one or few high‐abundance species. The dampening effect of migrant dominance on evenness–productivity relationships in many situations supports the notion that migrants concentrate in high‐productivity landscapes.

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Corrigendum to “Rainfall-driven resuspension of pathogenic Leptospira in a leptospirosis hotspot” [Sci. Total Environ. (2024) 168700] - R. Thibeaux; P. Genthon; R. Govan; N. Selmaoui-Folcher; C. Tramier; M. Kainiu; M.-E. Soupé-Gilbert; K. Wijesuriya; C. Goarant (Science of The Total Environment, 2026)

Geochronological and geochemical insights into episyenite metasomatic overprint in the Proterozoic Suomenniemi rapakivi granite complex (Finland) - Adam Abersteiner; O. Tapani Rämö; Alkis Kontonikas-Charos; Melissa Kharkongor; Nikolaos Karampelas; Sarah E. Gilbert; Ben Wade; Karolina Ambroziak-Murzyn; Jarred C. Lloyd; Christoph Beier; Stijn Glorie (Lithos, 2025)

Volcanoes to vugs: Demonstrating a FAIR geochemistry framework with a diverse application of major and trace element data through the AuScope EarthBank platform - Angus L. Nixon; Samuel C. Boone; Yoann Gréau; Fabian Kohlmann; Moritz Theile; Wayne Noble; Alexander Prent; John Foden; Steven Barnes; Ashlea N. Wainwright; Benjamin Wade; Karsten Goemann; et al. (Chemical Geology, 2025)

Climate Consideration in Environmental Effects Analyses on Federal Public Lands in the United States - Sarah E. Whipple; Sarah K. Carter; Tait K. Rutherford; Samuel E. Jordan; Richard J. Lehrter; Christopher T. Domschke; Megan A. Gilbert; Julian Reyes; Ella M. Samuel; Karen M. Schank; John C. Tull; David J. A. Wood (Environmental Management, 2025)

In situ Rb–Sr dating and REE analysis of glauconites and detrital feldspars from the Ediacaran/Cambrian strata: Centralian and Adelaide Superbasins, Australia - Cecilia Loyola; Juraj Farkaš; Alan S. Collins; Sarah E. Gilbert; Charles Verdel; Stefan C. Löhr; Glenn A. Brock; Graham A. Shields; Andre Baldermann; Ahmad Redaa; Morgan Blades; Darwinaji Subarkah; et al. (Precambrian Research, 2025)

Hidden decay of live trees in a tropical rain forest - Gregory S. Gilbert; Brant C. Faircloth; Travis C. Glenn; Javier O. Ballesteros; César A. Barrios‐Rodríguez; Ernesto Bonadies; Marjorie L. Cedeño‐Sánchez; Nohely J. Fossatti‐Caballero; José Moisés Pérez‐Suñiga; Mariam M. Trejos‐Rodríguez; Stephen P. Hubbell (Ecology, 2025)
The trunks of forest trees store massive amounts of carbon, but fungi actively and invisibly decay wood inside even seemingly healthy trees. Wood‐decay fungi are responsible for the loss of stored carbon in living trees, and they make trees susceptible to snapping and uprooting in storms. We used sonic tomography to measure the prevalence and severity of decay in 1744 live trees (≥20 cm diameter) of 171 species on the 50‐ha Forest Dynamics Plot on Barro Colorado Island, Panama. A median of 20% decay. Twenty percent of the combined basal area showed decay, representing a loss of approximately 1% of aboveground biomass. Larger trees more often showed internal decay, with one quarter of trees showing decay before reaching canopy height. Decay severity varied by species; 23% of species showed

Forest terpenes and stress: Examining the associations of filtered vs. non-filtered air in a real-life natural environment - Chaja M. Levy; Anne M. Riederer; Christopher D. Simpson; Amanda J. Gassett; Abigail J. Gilbert; Michael H. Paulsen; Lalith K. Silva; Deepak Bhandari; Cody A. Newman; Benjamin C. Blount; Peter H. Kahn; Gregory N. Bratman (Environmental Research, 2025)

Reanalysis of Samburupithecus reveals similarities to nyanzapithecines - Kelsey D. Pugh; Julie A. Strain; Christopher C. Gilbert (Journal of Human Evolution, 2025)

Adaptive sampling with PIXL on the Mars Perseverance rover - Peter R. Lawson; Tanya V. Kizovski; Michael M. Tice; Benton C. Clark; Scott J. VanBommel; David R. Thompson; Lawrence A. Wade; Robert W. Denise; Christopher M. Heirwegh; W. Timothy Elam; Mariek E. Schmidt; Yang Liu; et al. (Icarus, 2025)

Identifying Priority Science Information Needs for Managing Public Lands - Sarah K. Carter; Travis S. Haby; Ella M. Samuel; Alison C. Foster; Jennifer K. Meineke; Laine E. McCall; Malia K. Burton; Christopher T. Domschke; Leigh D. Espy; Megan A. Gilbert (Environmental Management, 2025)

Paleoenvironment, deposition conditions, and geochemical characteristics of the Permian Karoo hydrocarbon source rocks, Mid-Zambezi Basin, Zambia, based on paleontology and geochemistry studies: a review - Godfrey Peter Mweemba; Olubunmi C. Adeigbe; Gilbert M. Chongwain; Khady Ndeye Ndiaye (Arabian Journal of Geosciences, 2025)

Inhibition of soluble epoxide hydrolase ameliorates cerebral blood flow autoregulation and cognition in alzheimer's disease and diabetes-related dementia rat models - Chengyun Tang; Jane J. Border; Huawei Zhang; Andrew Gregory; Shan Bai; Xing Fang; Yedan Liu; Shaoxun Wang; Sung Hee Hwang; Wenjun Gao; Gilbert C. Morgan; Jhania Smith; et al. (GeroScience, 2025)

A holo-omics analysis shows how sugar kelp can boost gut health in Atlantic salmon - Jacob A. Rasmussen; Annette Bernhard; Laurène A. Lecaudey; Varsha Kale; Germana Baldi; Lene S. Myrmel; Martin Hansen; Jaelle C. Brealey; Sarah S.T. Mak; Ida B. Nielsen; Lorna Richardson; Lise Madsen; et al. (Aquaculture, 2025)

Additional analyses of stem catarrhine and hominoid dental morphology support Kapi ramnagarensis as a stem hylobatid - Christopher C. Gilbert; Alejandra Ortiz; Kelsey D. Pugh; Christopher J. Campisano; Biren A. Patel; Ningthoujam Premjit Singh; John G. Fleagle; Rajeev Patnaik (Journal of Human Evolution, 2025)

Mean plant toxicity modulates the effects of plant defense variability - Vincent S. Pan; Kadeem J. Gilbert; William C. Wetzel (Ecology, 2025)
Plant trait variation is thought to suppress herbivore performance, but experiments typically manipulate only a single mean level of the trait. We manipulated the mean and variation of the concentration of a plant toxin in a model plant–herbivore system across three field and greenhouse experiments. Plants with leaves painted with a higher mean toxin concentration exhibited increased fitness and resistance to herbivores; however, at high mean concentrations, variation reduced the defensive effect, while at lower mean concentrations, variation enhanced it. This reversal aligns with models that include herbivore food selectivity, but our simulations revealed that the benefits of food selectivity for herbivores were minimal. Instead, nonlinear averaging and physiological tracking effects likely drove patterns in plant fitness and resistance to herbivores. We suggest that high defense variation in plants may be a widespread defensive phenotype, but for well‐defended plants, variation may inadvertently promote herbivore niche expansion.

Large Differences in Herbivore Performance Emerge From Simple Herbivore Behaviours and Fine‐Scale Spatial Heterogeneity in Phytochemistry - Vincent S. Pan; Enakshi Ghosh; Paul J. Ode; William C. Wetzel; Kadeem J. Gilbert; Ian S. Pearse (Ecology Letters, 2025)
Patterns of phytochemistry localisation in plant tissues are diverse within and across leaves. These spatial heterogeneities are important to the fitness of herbivores, but their effects on herbivore foraging and dietary experience remain elusive. We manipulated the spatial variance and clusteredness of a plant toxin in a synthetic diet landscape on which individual caterpillars fed. We monitored caterpillars with cameras across most of their larval development. Caterpillars that fed on diets with a lower spatial variance and more clustered arrangement of toxins had overall worse performance, mostly because those caterpillars ate less, moved more, ingested more toxin, or failed to physiologically acclimate. Using empirically parameterised individual‐based models, we found that differences in movement away from, not towards, less toxic food drove a body size‐dependent effect of clusteredness. Hence, the spatial pattern of phytochemicals itself, beyond mean concentration, can have important consequences for herbivores through complex interactions with herbivore foraging.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Double dating sedimentary sequences using new applications of in-situ laser ablation analysis - Darwinaji Subarkah; Angus L. Nixon; Sarah E. Gilbert; Alan S. Collins; Morgan L. Blades; Alexander Simpson; Jarred C. Lloyd; Georgina M. Virgo; Juraj Farkaš (Lithos, 2024)

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Influence of habitat and baiting strategy on oral rabies vaccine bait uptake by raccoons in the southeastern United States - Jacob E. Hill; Madison L. Miller; Richard B. Chipman; Amy T. Gilbert; James C. Beasley; Guha Dharmarajan; Olin E. Rhodes (Applied Animal Behaviour Science, 2024)

Kinetic Modeling for BT200 to Predict the Level of Plasma-Derived Coagulation Factor VIII in Humans - Min-Soo Kim; Dagmar M. Hajducek; James C. Gilbert; Alfonso Iorio; Bernd Jilma; Andrea N. Edginton (The AAPS Journal, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Understanding the risks of co-exposures in a changing world: a case study of dual monitoring of the biotoxin domoic acid and Vibrio spp. in Pacific oyster - Alle A. Y. Lie; Amity G. Zimmer-Faust; Rachel E. Diner; Emily Kunselman; Zachary Daniel; Kathryn Van Artsdalen; Mariana C. Salas Garcia; Jack A. Gilbert; Dana Shultz; Jeff Chokry; Kylie Langlois; Jayme Smith (Environmental Monitoring and Assessment, 2024)

Post-mortem findings in neonatal C57BL/6J pups - S. Capas-Peneda; G. Munhoz Morello; J.B. Prins; I.A.S. Olsson; C. Gilbert (Journal of Comparative Pathology, 2024)

Home range and resource selection of Virginia opossums in the rural southeastern United States - Jacob E. Hill; David A. Bernasconi; Richard B. Chipman; Amy T. Gilbert; James C. Beasley; Olin E. Rhodes; Guha Dharmarajan (Mammal Research, 2024)

Rainfall-driven resuspension of pathogenic Leptospira in a leptospirosis hotspot - R. Thibeaux; P. Genthon; R. Govan; N. Selmaoui-Folcher; C. Tramier; M. Kainiu; M.-E. Soupé-Gilbert; K. Wijesuriya; C. Goarant (Science of The Total Environment, 2024)

Global Patterns of Metal and Other Element Enrichment in Bog and Fen Peatlands - Chetwynd Osborne; Spencer Gilbert-Parkes; Graeme Spiers; Louis James Lamit; Erik A. Lilleskov; Nathan Basiliko; Shaun Watmough; Roxanne Andersen; Rebekka E. Artz; Brian W. Benscoter; Luca Bragazza; Suzanna L. Bräuer; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Periconceptional and Prenatal Exposure to Metals and Extracellular Vesicle and Particle miRNAs in Human Milk: A Pilot Study - Caitlin G. Howe; David A. Armstrong; Meghan E. Muse; Diane Gilbert-Diamond; Jiang Gui; Anne G. Hoen; Thomas J. Palys; Roxanna L. Barnaby; Bruce A. Stanton; Brian P. Jackson; Brock C. Christensen; Margaret R. Karagas (Exposure and Health, 2023)

Implications of outgroup selection in the phylogenetic inference of hominoids and fossil hominins - Nicholas W. Post; Christopher C. Gilbert; Kelsey D. Pugh; Carrie S. Mongle (Journal of Human Evolution, 2023)

Peptide-based pore formation and cell membrane deformation: European Biophysics Journal Prizes at EBSA 2023 - Robert J. C. Gilbert (European Biophysics Journal, 2023)

Experimental investigation on the shear behaviour of the brickwork-backfill interface in masonry arch bridges - Bowen Liu; Anastasios Drougkas; Vasilis Sarhosis; Colin C. Smith; Matthew Gilbert (Engineering Structures, 2023)

Assessment of pixel-oriented k-NN machine learning algorithm performance for the interannual remote sensing monitoring of eelgrass beds at the mouth of the Romaine - P. Lemieux; C. Lalumière; N. Fugaru; J.-P. Gilbert; A. Tremblay (Environmental Monitoring and Assessment, 2023)
Eelgrass cover extent is among the most reliable indicators for measuring changes in coastal ecosystems. Eelgrass has colonized the mouth of the Romaine River and has become a part of environmental monitoring there since 2013. The presence of eelgrass in this area is an essential factor for the early detection of changes in the Romaine coastal ecosystem. This will act as a trigger for an appropriate environmental response to preserve ecosystem health. In this paper, a cost- and time-efficient workflow for such spatial monitoring is proposed using a pixel-oriented k-NN algorithm. It can then be applied to multiple modellers to efficiently map the eelgrass cover. Training data were collected to define key variables for segmentation and k-NN classification, providing greater edge detection for the presence of eelgrass. The study highlights that remote sensing and training data must be acquired under similar conditions, replicating methodologies for collecting data on the ground. Similar approaches must be used for the zonal statistic requirements of the monitoring area. This will allow a more accurate and reliable assessment of eelgrass beds over time. An overall accuracy of over 90% was achieved for eelgrass detection for each year of monitoring.

Occurrence of the endangered whitespotted eagle ray Aetobatus narinari around the Lesser Antilles island of Saint Kitts: a photo-identification study - Anne Conan; Michelle M. Dennis; Kathleen Gilbert; Eva Lenain; Stephan Bruns; Aaron C. Henderson (Environmental Biology of Fishes, 2023)

In vitro reduction of Escherichia coli biofilm mass by platelet-rich plasma lysate (PRP-L) - Bryan C Stallings; Jessica Gilbert; Megan E Jacob; Lauren V Schnabel; Jose Len; Sara K Lyle (Journal of Equine Veterinary Science, 2023)

Substrate type induces plastic responses in the craniofacial morphology of a winnowing cichlid - Michelle C. Gilbert; Sofia N. Piggott; R. Craig Albertson (Hydrobiologia, 2023)
Understanding how local populations respond to specific changes in the environment can help us better predict how populations respond to such change. With this topic in mind, we followed up on a previous study by exploring the capabilities of a Geophagini cichlid, known for its unique feeding strategy, to mount a plastic response. We exposed Satanoperca daemon , a winnowing cichlid, to three different substrate types, two of which encouraged winnowing behaviors and a third that prevented winnowing entirely. Using geometric morphometrics, we quantified aspects of craniofacial anatomy to test for morphological differences between the treatments and to test for the integration of different traits across the head. We found significant differences across our experimental populations in both shape and disparity. We report evidence in support of wide-spread integration across craniofacial traits. A notable exception to this pattern was the epibranchial lobe, a structure unique to the Geophagini, which exhibited more modular variation. Since anthropogenic alterations such as the damming of rivers can impact substrate type, these data offer insights into how Geophagini cichlids may respond to environmental change. In addition, this work further illuminates the functional morphology of winnowing foraging behaviors.

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Belize Blue Carbon: Establishing a national carbon stock estimate for mangrove ecosystems - Hannah K. Morrissette; Stacy K. Baez; Lisa Beers; Nadia Bood; Ninon D. Martinez; Kevin Novelo; Gilbert Andrews; Luis Balan; C. Scott Beers; Sumeet A. Betancourt; Reynel Blanco; Eeryn Bowden; et al. (Science of The Total Environment, 2023)

Interspecific oral rabies vaccine bait competition in the Southeast United States - Wesley C. Dixon; Jacob E. Hill; Richard B. Chipman; Amy J. Davis; Amy T. Gilbert; James C. Beasley; Olin E. Rhodes; Guha Dharmarajan (Applied Animal Behaviour Science, 2023)

Effects of ants on riparian poplars: an ex situ experiment of biotic interaction - D. Corenblit; B. Corbara; R. Cereghino; A. Dejean; P. Duran; V. Garófano-Gómez; F. Gilbert; E. González-Sargas; F. Julien; L. Lambs; C. Mainguin; L. Mazal; et al. (Arthropod-Plant Interactions, 2023)

Multiple‐brooding rockfishes ( Sebastes spp.) can utilize stored sperm from individual sires to fertilize consecutive broods - Neosha S Kashef; David M. Stafford; Susan M. Sogard; John C. Garza; John C. Field; Elizabeth A. Gilbert‐Horvath (Journal of Fish Biology, 2023)
Viviparous rockfishes ( Sebastes spp., family Scorpaenidae) mate and store sperm in the ovaries for several months prior to fertilization, as oocytes develop for the parturition season. Although multiple paternity has been documented in single‐brooding rockfishes, paternity in consecutive broods of multiple‐brooding species has not been studied. Analyses of multilocus microsatellite genotypes in both residual larvae left in the ovary from a previous parturition and upcoming fertilized broods in the same ovary demonstrated evidence of the same sires in consecutive broods in chilipepper ( Sebastes goodei ) and speckled ( Sebastes ovalis ) rockfishes. One S. goodei mother showed evidence of multiple paternity from the same two sires in both consecutive broods. The ability to retain sperm, even after a parturition event, for use in subsequent broods, confers an advantage to ensure fertilization and allows for extension of the parturition season. This life‐history strategy provides a bet‐hedging advantage in the California Current system, an environmentally dynamic ecosystem where larval survivorship and subsequent recruitment to adult populations can vary temporally by orders of magnitude.

Community Patterns and Environmental Associations for the Early Life Stages of Fishes in a Highly Transformed Estuary - Gonzalo C. Castillo; Trishelle Tempel; Steven B. Slater; Brian Mahardja; Morgan D. Gilbert (Estuaries and Coasts, 2023)
Estuaries are important fish nursery areas, yet little is known of how environmental forcing influences estuarine fishes during their early life stages. We analyzed environmental and larval-juvenile fish community data in the upper San Francisco Estuary (SFE) from spring to early summer 1995–2017, to better understand drivers of spatiotemporal community patterns in this highly modified estuary. We evaluated community patterns based on the relative abundance and diversity of native and introduced fish in the SFE and their predominant distribution (pelagic, demersal). The upper SFE experienced a downward trend of freshwater outflow and upward trends of temperature and salinity intrusion. Fish relative abundance only showed long-term downtrends for native and introduced pelagic fish groups. The most influential habitat components for relative abundance and diversity of fish groups were in decreasing order: temperature, salinity, Secchi depth, bottom depth, and zooplankton biomass. Early life stages of native and introduced fishes were generally segregated spatially and temporally, with native fishes more associated with cooler, saltier, and higher turbidity habitats during early to mid-spring compared to introduced fishes during late spring to early summer. Community ordination showed that environmental (temperature, salinity, outflow, Secchi depth, and zooplankton biomass) and spatiotemporal factors (month and depth), explained nearly 40% of the total variance. Our results suggest that the shorter duration of planktonic and nektonic stages of demersal fish groups results in higher resiliency compared to pelagic fishes. The declining abundance of pelagic fishes overall seems to be linked to drought effects and human-induced synergistic interactions intensified by climate change.

Evaluation of phosphorus runoff from sandy soils under conservation tillage with surface broadcasted recovered phosphates - Clement D.D. Sohoulande; Ariel A. Szogi; Kenneth C. Stone; Gilbert C. Sigua; Jerry H. Martin; Paul D. Shumaker; Phil J. Bauer (Journal of Environmental Management, 2023)

Mineralogical, magnetic and geochemical data constrain the pathways and extent of weathering of mineralized sedimentary rocks - Sergio Carrero; Sarah P. Slotznick; Sirine C. Fakra; M. Cole Sitar; Sharon E. Bone; Jeffrey L. Mauk; Andrew H. Manning; Nicholas L. Swanson-Hysell; Kenneth H Williams; Jillian F. Banfield; Benjamin Gilbert (Geochimica et Cosmochimica Acta, 2023)

Limited recovery following a massive seagrass decline in subarctic eastern Canada - Mélanie‐Louise Leblanc; Mary I. O'Connor; Zou Zou A. Kuzyk; Fanny Noisette; Kaleigh E. Davis; Ernie Rabbitskin; Laura‐Lee Sam; Urs Neumeier; Rémi Costanzo; Jens K. Ehn; David Babb; C. Julián Idrobo; et al. (Global Change Biology, 2023)
Over the last few decades, there has been an increasing recognition for seagrasses' contribution to the functioning of nearshore ecosystems and climate change mitigation. Nevertheless, seagrass ecosystems have been deteriorating globally at an accelerating rate during recent decades. In 2017, research into the condition of eelgrass ( Zostera marina ) along the eastern coast of James Bay, Canada, was initiated in response to reports of eelgrass decline by the Cree First Nations of Eeyou Istchee. As part of this research, we compiled and analyzed two decades of eelgrass cover data and three decades of eelgrass monitoring data (biomass and density) to detect changes and assess possible environmental drivers. We detected a major decline in eelgrass condition between 1995 and 1999, which encompassed the entire east coast of James Bay. Surveys conducted in 2019 and 2020 indicated limited changes post‐decline, for example, low eelgrass cover ( 50% cover in eastern James Bay since 1995, representing the largest scale eelgrass decline documented in eastern Canada since the massive die‐off event that occurred in the 1930s along the North Atlantic coast. Using biomass data collected since 1982, but geographically limited to the sector of the coast near the regulated La Grande River, generalized additive modeling revealed eelgrass meadows are affected by local sea surface temperature, early ice breakup, and higher summer freshwater discharge. Our results caution against assuming subarctic seagrass ecosystems have avoided recent global declines or will benefit from ongoing climate warming.

Determining resource intake of a nonnative fish highlights potential predatory and competitive interactions - S. C. Hedden; K. B. Gido; C. K. Hedden; C. A. Pennock; B. R. Duran; B. A. Hines; E. I. Gilbert; M. C. McKinstry; S. L. Durst; N. R. Franssen (Biological Invasions, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Ecological consequences of large herbivore exclusion in an A frican savanna: 12 years of data from the UHURU experiment - Jesse M. Alston; Courtney G. Reed; Leo M. Khasoha; Bianca R. P. Brown; Gilbert Busienei; Nathaniel Carlson; Tyler C. Coverdale; Megan Dudenhoeffer; Marissa A. Dyck; John Ekeno; Abdikadir A. Hassan; Rhianna Hohbein; et al. (Ecology, 2022)
Diverse communities of large mammalian herbivores (LMH), once widespread, are now rare. LMH exert strong direct and indirect effects on community structure and ecosystem functions, and measuring these effects is important for testing ecological theory and for understanding past, current, and future environmental change. This in turn requires long‐term experimental manipulations, owing to the slow and often nonlinear responses of populations and assemblages to LMH removal. Moreover, the effects of particular species or body‐size classes within diverse LMH guilds are difficult to pinpoint, and the magnitude and even direction of these effects often depends on environmental context. Since 2008, we have maintained the Ungulate Herbivory Under Rainfall Uncertainty (UHURU) experiment, a series of size‐selective LMH exclosures replicated across a rainfall/productivity gradient in a semiarid Kenyan savanna. The goals of the UHURU experiment are to measure the effects of removing successively smaller size classes of LMH (mimicking the process of size‐biased extirpation) and to establish how these effects are shaped by spatial and temporal variation in rainfall. The UHURU experiment comprises three LMH‐exclusion treatments and an unfenced control, applied to nine randomized blocks of contiguous 1‐ha plots ( n = 36). The fenced treatments are MEGA (exclusion of megaherbivores, elephant and giraffe), MESO (exclusion of herbivores ≥40 kg), and TOTAL (exclusion of herbivores ≥5 kg). Each block is replicated three times at three sites across the 20‐km rainfall gradient, which has fluctuated over the course of the experiment. The first 5 years of data were published previously ( Ecological Archives E095‐064) and have been used in numerous studies. Since that publication, we have (1) continued to collect data following the original protocols, (2) improved the taxonomic resolution and accuracy of plant and small‐mammal identifications, and (3) begun collecting several new data sets. Here, we present updated and extended raw data from the first 12 years of the UHURU experiment (2008–2019). Data include daily rainfall data throughout the experiment; annual surveys of understory plant communities; annual censuses of woody‐plant communities; annual measurements of individually tagged woody plants; monthly monitoring of flowering and fruiting phenology; every‐other‐month small‐mammal mark–recapture data; and quarterly large‐mammal dung surveys. There are no copyright restrictions; notification of when and how data are used is appreciated and users of UHURU data should cite this data paper when using the data.

Sorbents for treatment of hereditary hemochromatosis - Anna Wilson; Leslie Laguna; Lansten Yew; Kerry Kao; Kathryn Bauguess; Jiaying Wang; Sofia de la O; Grant Romme; William Gilbert; Ana Rita C. Morais; Jian Qian; Cory J. Berkland; et al. (Medicinal Chemistry Research, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A Global Ocean Oxygen Database and Atlas for Assessing and Predicting Deoxygenation and Ocean Health in the Open and Coastal Ocean - Marilaure Grégoire; Véronique Garçon; Hernan Garcia; Denise Breitburg; Kirsten Isensee; Andreas Oschlies; Maciej Telszewski; Alexander Barth; Henry C. Bittig; Jacob Carstensen; Thierry Carval; Fei Chai; et al. (Frontiers in Marine Science, 2021)
In this paper, we outline the need for a coordinated international effort toward the building of an open-access Global Ocean Oxygen Database and ATlas (GO 2 DAT) complying with the FAIR principles (Findable, Accessible, Interoperable, and Reusable). GO 2 DAT will combine data from the coastal and open ocean, as measured by the chemical Winkler titration method or by sensors (e.g., optodes, electrodes) from Eulerian and Lagrangian platforms (e.g., ships, moorings, profiling floats, gliders, ships of opportunities, marine mammals, cabled observatories). GO 2 DAT will further adopt a community-agreed, fully documented metadata format and a consistent quality control (QC) procedure and quality flagging (QF) system. GO 2 DAT will serve to support the development of advanced data analysis and biogeochemical models for improving our mapping, understanding and forecasting capabilities for ocean O 2 changes and deoxygenation trends. It will offer the opportunity to develop quality-controlled data synthesis products with unprecedented spatial (vertical and horizontal) and temporal (sub-seasonal to multi-decadal) resolution. These products will support model assessment, improvement and evaluation as well as the development of climate and ocean health indicators. They will further support the decision-making processes associated with the emerging blue economy, the conservation of marine resources and their associated ecosystem services and the development of management tools required by a diverse community of users (e.g., environmental agencies, aquaculture, and fishing sectors). A better knowledge base of the spatial and temporal variations of marine O 2 will improve our understanding of the ocean O 2 budget, and allow better quantification of the Earth’s carbon and heat budgets. With the ever-increasing need to protect and sustainably manage ocean services, GO 2 DAT will allow scientists to fully harness the increasing volumes of O 2 data already delivered by the expanding global ocean observing system and enable smooth incorporation of much higher quantities of data from autonomous platforms in the open ocean and coastal areas into comprehensive data products in the years to come. This paper aims at engaging the community (e.g., scientists, data managers, policy makers, service users) toward the development of GO 2 DAT within the framework of the UN Global Ocean Oxygen Decade (GOOD) program recently endorsed by IOC-UNESCO. A roadmap toward GO 2 DAT is proposed highlighting the efforts needed (e.g., in terms of human resources).

The dilemma of Guinea grass (Megathyrsus maximus): a valued pasture grass and a highly invasive species - Aaron C. Rhodes; Robert M. Plowes; John A. Goolsby; John F. Gaskin; Boaz Musyoka; Paul-André Calatayud; Massimo Cristofaro; Eric D. Grahmann; Dino J. Martins; Lawrence E. Gilbert (Biological Invasions, 2021)

Historical population declines prompted significant genomic erosion in the northern and southern white rhinoceros ( Ceratotherium simum ) - Fátima Sánchez‐Barreiro; Shyam Gopalakrishnan; Jazmín Ramos‐Madrigal; Michael V. Westbury; Marc de Manuel; Ashot Margaryan; Marta M. Ciucani; Filipe G. Vieira; Yannis Patramanis; Daniela C. Kalthoff; Zena Timmons; Thomas Sicheritz‐Pontén; et al. (Molecular Ecology, 2021)
Large vertebrates are extremely sensitive to anthropogenic pressure, and their populations are declining fast. The white rhinoceros ( Ceratotherium simum ) is a paradigmatic case: this African megaherbivore has suffered a remarkable decline in the last 150 years due to human activities. Its subspecies, the northern (NWR) and the southern white rhinoceros (SWR), however, underwent opposite fates: the NWR vanished quickly, while the SWR recovered after the severe decline. Such demographic events are predicted to have an erosive effect at the genomic level, linked to the extirpation of diversity, and increased genetic drift and inbreeding. However, there is little empirical data available to directly reconstruct the subtleties of such processes in light of distinct demographic histories. Therefore, we generated a whole‐genome, temporal data set consisting of 52 resequenced white rhinoceros genomes, representing both subspecies at two time windows: before and during/after the bottleneck. Our data reveal previously unknown population structure within both subspecies, as well as quantifiable genomic erosion. Genome‐wide heterozygosity decreased significantly by 10% in the NWR and 36% in the SWR, and inbreeding coefficients rose significantly by 11% and 39%, respectively. Despite the remarkable loss of genomic diversity and recent inbreeding it suffered, the only surviving subspecies, the SWR, does not show a significant accumulation of genetic load compared to its historical counterpart. Our data provide empirical support for predictions about the genomic consequences of shrinking populations, and our findings have the potential to inform the conservation efforts of the remaining white rhinoceroses.

Animal Borne Ocean Sensors – AniBOS – An Essential Component of the Global Ocean Observing System - Clive R. McMahon; Fabien Roquet; Sophie Baudel; Mathieu Belbeoch; Sophie Bestley; Clint Blight; Lars Boehme; Fiona Carse; Daniel P. Costa; Michael A. Fedak; Christophe Guinet; Robert Harcourt; et al. (Frontiers in Marine Science, 2021)
Marine animals equipped with biological and physical electronic sensors have produced long-term data streams on key marine environmental variables, hydrography, animal behavior and ecology. These data are an essential component of the Global Ocean Observing System (GOOS). The Animal Borne Ocean Sensors (AniBOS) network aims to coordinate the long-term collection and delivery of marine data streams, providing a complementary capability to other GOOS networks that monitor Essential Ocean Variables (EOVs), essential climate variables (ECVs) and essential biodiversity variables (EBVs). AniBOS augments observations of temperature and salinity within the upper ocean, in areas that are under-sampled, providing information that is urgently needed for an improved understanding of climate and ocean variability and for forecasting. Additionally, measurements of chlorophyll fluorescence and dissolved oxygen concentrations are emerging. The observations AniBOS provides are used widely across the research, modeling and operational oceanographic communities. High latitude, shallow coastal shelves and tropical seas have historically been sampled poorly with traditional observing platforms for many reasons including sea ice presence, limited satellite coverage and logistical costs. Animal-borne sensors are helping to fill that gap by collecting and transmitting in near real time an average of 500 temperature-salinity-depth profiles per animal annually and, when instruments are recovered (∼30% of instruments deployed annually, n = 103 ± 34), up to 1,000 profiles per month in these regions. Increased observations from under-sampled regions greatly improve the accuracy and confidence in estimates of ocean state and improve studies of climate variability by delivering data that refine climate prediction estimates at regional and global scales. The GOOS Observations Coordination Group (OCG) reviews, advises on and coordinates activities across the global ocean observing networks to strengthen the effective implementation of the system. AniBOS was formally recognized in 2020 as a GOOS network. This improves our ability to observe the ocean’s structure and animals that live in them more comprehensively, concomitantly improving our understanding of global ocean and climate processes for societal benefit consistent with the UN Sustainability Goals 13 and 14: Climate and Life below Water. Working within the GOOS OCG framework ensures that AniBOS is an essential component of an integrated Global Ocean Observing System.

Does a Trawl Ban Benefit Commercially Important Decapoda and Stomatopoda in Hong Kong? - Lily S. R. Tao; Gilbert C. S. Lui; Kingsley J. H. Wong; Tommy T. Y. Hui; Yanny K. Y. Mak; Ronia C.-t Sham; Jason K. C. Yau; William W. L. Cheung; Kenneth M. Y. Leung (Ecosystems, 2021)
Crustaceans were among the most valuable fishery resources in Hong Kong. However, the unrestricted and intensive use of different fishing gears, especially bottom trawling, has led to the depletion of commercially important crustaceans in Hong Kong since the 1980s. This study investigated whether commercial crustaceans recovered after the implementation of a permanent Hong Kong-wide trawl ban that began on December 31, 2012. Standardized field surveys were conducted using a commercial shrimp trawler at two sites in eastern and western waters of Hong Kong before (2004) and after the trawl ban (2013–2014 and 2015–2016) and two sites in southern waters after the trawl ban. Diversity, mean size, abundance, biomass and level of disturbance of commercial crustaceans from the three periods were investigated. The eastern waters exhibited an increased diversity of crustacean assemblages in Inner Tolo, and a higher abundance and biomass of crabs were detected in Outer Tolo after the trawl ban. Reduced disturbance, higher diversity in crustacean assemblages and greater abundance and biomass of predatory crabs were observed after the trawl ban in the outer estuary of western waters, and increased abundance and biomass of shrimp were detected in the inner estuary of western waters. No temporal or negative changes were detected in the southeast and southern waters of Lamma Island. The various responses of crustacean assemblages in Hong Kong waters revealed the critical role of complex interactions among multiple stresses, such as ongoing reclamation works, illegal trawling activities and increased fishing efforts using other (legal) fishing methods.

Using DNA to distinguish between faeces of Dugong dugon and Chelonia mydas: non-invasive sampling for IUCN-listed marine megafauna - S. J. Tol; M. Harrison; R. Groom; J. Gilbert; D. Blair; R. Coles; B. C. Congdon (Conservation Genetics Resources, 2021)

Abundance and biogeography of methanogenic and methanotrophic microorganisms across European streams - Magdalena Nagler; Nadine Praeg; Georg H. Niedrist; Katrin Attermeyer; Núria Catalán; Francesca Pilotto; Catherine Gutmann Roberts; Christoph Bors; Stefano Fenoglio; Miriam Colls; Sophie Cauvy‐Fraunié; Brian Doyle; et al. (Journal of Biogeography, 2021)
Aim Although running waters are getting recognized as important methane sources, large‐scale geographical patterns of microorganisms controlling the net methane balance of streams are still unknown. Here we aim at describing community compositions of methanogenic and methanotrophic microorganisms at large spatial scales and at linking their abundances to potential sediment methane production (PMP) and oxidation rates (PMO). Location The study spans across 16 European streams from northern Spain to northern Sweden and from western Ireland to western Bulgaria. Taxon Methanogenic archaea and methane‐oxidizing microorganisms. Methods To provide a geographical overview of both groups in a single approach, microbial communities and abundances were investigated via 16S rRNA gene sequencing, extracting relevant OTUs based on literature; both groups were quantified via quantitative PCR targeting mcrA and pmoA genes and studied in relation to environmental parameters, sediment PMP and PMO, and land use. Results Diversity of methanogenic archaea was higher in warmer streams and of methanotrophic communities in southern sampling sites and in larger streams. Anthropogenically altered, warm and oxygen‐poor streams were dominated by the highly efficient methanogenic families Methanospirillaceae , Methanosarcinaceae and Methanobacteriaceae , but did not harbour any specific methanotrophic organisms. Contrastingly, sediment communities in colder, oxygen‐rich waters with little anthropogenic impact were characterized by methanogenic Methanosaetaceae , Methanocellaceae and Methanoflorentaceae and methanotrophic Methylococcaceae and Cd . Methanoperedens. Representatives of the methanotrophic Crenotrichaceae and Methylococcaceae as well as the methanogenic Methanoregulaceae were characteristic for environments with larger catchment area and higher discharge. PMP increased with increasing abundance of methanogenic archaea, while PMO rates did not show correlations with abundances of methane‐oxidizing bacteria. Main conclusions Methanogenic and methanotrophic communities grouping into three habitat types suggest that future climate‐ and land use changes may influence the prevailing microbes involved in the large‐scale stream‐related methane cycle, favouring the growth of highly efficient hydrogenotrophic methane producers. Based on these results, we expect global change effect on PMP rates to especially impact rivers adjacent to anthropogenically disturbed land uses.

An assessment of early 20th century Antarctic pressure reconstructions using historical observations - Ryan L. Fogt; Connor P. Belak; Julie M. Jones; Laura C. Slivinski; Gilbert P. Compo (International Journal of Climatology, 2021)
While gridded seasonal pressure reconstructions poleward of 60°S extending back to 1905 have been recently completed, their skill has not been assessed prior to 1958. To provide a more thorough evaluation of the skill and performance in the early 20th century, these reconstructions are compared to other gridded datasets, historical data from early Antarctic expeditions, ship records, and temporary bases. Overall, the comparison confirms that the reconstruction uncertainty of 2–4 hPa (evaluated after 1979) over the Southern Ocean is a valid estimate of the reconstruction error in the early 20th century. Over the interior and near the coast of Antarctica, direct comparisons with historical data are challenged by elevation‐based reductions to sea level pressure. In a few cases, a simple linear adjustment of the reconstruction to sea level matches the historical data well, but in other cases, the differences remain greater than 10 hPa. Despite these large errors, comparisons with continuous multi‐season observations demonstrate that aspects of the interannual variability are often still captured, suggesting that the reconstructions have skill representing variations on this timescale, even if it is difficult to determine how well they capture the mean pressure at these higher elevations. Additional comparisons with various 20th‐century reanalysis products demonstrate the value of assimilating the historical observations in these datasets, which acts to substantially reduce the reanalysis ensemble spread, and bring the reanalysis ensemble mean within the reconstruction and observational uncertainty.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Genetic, clinical, molecular, and pathogenic aspects of the South Asian–specific polymorphic MYBPC3Δ25bp variant - Mohammed Arif; Pooneh Nabavizadeh; Taejeong Song; Darshini Desai; Rohit Singh; Sholeh Bazrafshan; Mohit Kumar; Yigang Wang; Richard J. Gilbert; Perundurai S. Dhandapany; Richard C. Becker; Evangelia G. Kranias; et al. (Biophysical Reviews, 2020)

Rolling stones gather moss: movement and longevity of moss balls on an Alaskan glacier - Scott Hotaling; Timothy C. Bartholomaus; Sophie L. Gilbert (Polar Biology, 2020)

Ancient DNA suggests modern wolves trace their origin to a Late Pleistocene expansion from Beringia - Liisa Loog; Olaf Thalmann; Mikkel‐Holger S. Sinding; Verena J. Schuenemann; Angela Perri; Mietje Germonpré; Herve Bocherens; Kelsey E. Witt; Jose A. Samaniego Castruita; Marcela S. Velasco; Inge K. C. Lundstrøm; Nathan Wales; et al. (Molecular Ecology, 2020)
Grey wolves ( Canis lupus ) are one of the few large terrestrial carnivores that have maintained a wide geographical distribution across the Northern Hemisphere throughout the Pleistocene and Holocene. Recent genetic studies have suggested that, despite this continuous presence, major demographic changes occurred in wolf populations between the Late Pleistocene and early Holocene, and that extant wolves trace their ancestry to a single Late Pleistocene population. Both the geographical origin of this ancestral population and how it became widespread remain unknown. Here, we used a spatially and temporally explicit modelling framework to analyse a data set of 90 modern and 45 ancient mitochondrial wolf genomes from across the Northern Hemisphere, spanning the last 50,000 years. Our results suggest that contemporary wolf populations trace their ancestry to an expansion from Beringia at the end of the Last Glacial Maximum, and that this process was most likely driven by Late Pleistocene ecological fluctuations that occurred across the Northern Hemisphere. This study provides direct ancient genetic evidence that long‐range migration has played an important role in the population history of a large carnivore, and provides insight into how wolves survived the wave of megafaunal extinctions at the end of the last glaciation. Moreover, because Late Pleistocene grey wolves were the likely source from which all modern dogs trace their origins, the demographic history described in this study has fundamental implications for understanding the geographical origin of the dog.

Interaction of APOE, cerebral blood flow, and cortical thickness in the entorhinal cortex predicts memory decline - Chelsea C. Hays; Zvinka Z. Zlatar; M.J. Meloy; Mark W. Bondi; Paul E. Gilbert; Thomas Liu; Jonathan L. Helm; Christina E. Wierenga (Brain Imaging and Behavior, 2020)

Species niches, not traits, determine abundance and occupancy patterns: A multi‐site synthesis - Nicholas A. C. Marino; Régis Céréghino; Benjamin Gilbert; Jana S. Petermann; Diane S. Srivastava; Paula M. de Omena; Fabiola Ospina Bautista; Laura Melissa Guzman; Gustavo Q. Romero; M. Kurtis Trzcinski; Ignacio M. Barberis; Bruno Corbara; et al. (Global Ecology and Biogeography, 2020)
Aim Locally abundant species are usually widespread, and this pattern has been related to properties of the niches and traits of species. However, such explanations fail to account for the potential of traits to determine species niches and often overlook statistical artefacts. Here, we examine how trait distinctiveness determines the abilities of species to exploit either common habitats (niche position) or a range of habitats (niche breadth) and how niche position and breadth, in turn, affect abundance and occupancy. We also examine how statistical artefacts moderate these relationships. Location Sixteen sites in the Neotropics. Time period 1993–2014. Major taxa studied Aquatic invertebrates from tank bromeliads. Methods We measured the environmental niche position and breadth of each species and calculated its trait distinctiveness as the average trait difference from all other species at each site. Then, we used a combination of structural equation models and a meta‐analytical approach to test trait–niche relationships and a null model to control for statistical artefacts. Results The trait distinctiveness of each species was unrelated to its niche properties, abundance and occupancy. In contrast, niche position was the main predictor of abundance and occupancy; species that used the most common environmental conditions found across bromeliads were locally abundant and widespread. Contributions of niche breadth to such patterns were attributable to statistical artefacts, indicating that effects of niche breadth might have been overestimated in previous studies. Main conclusions Our study reveals the generality of niche position in explaining one of the most common ecological patterns. The robustness of this result is underscored by the geographical extent of our study and our control of statistical artefacts. We call for a similar examination across other systems, which is an essential task to understand the drivers of commonness across the tree of life.

Implications of different nitrogen input sources for potential production and carbon flux estimates in the coastal Gulf of Mexico (GOM) and Korean Peninsula coastal waters - Jongsun Kim; Piers Chapman; Gilbert Rowe; Steven F. DiMarco; Daniel C. O. Thornton (Ocean Science, 2020)
The coastal Gulf of Mexico (GOM) and coastal sea off the Korean Peninsula (CSK) both suffer from human-induced eutrophication. We used a nitrogen (N) mass balance model in two different regions with different nitrogen input sources to estimate organic carbon fluxes and predict future carbon fluxes under different model scenarios. The coastal GOM receives nitrogen predominantly from the Mississippi and Atchafalaya rivers and atmospheric nitrogen deposition is only a minor component in this region. In the CSK, groundwater and atmospheric nitrogen deposition are more important controlling factors. Our model includes the fluxes of nitrogen to the ocean from the atmosphere, groundwater and rivers, based on observational and literature data, and identifies three zones (brown, green and blue waters) in the coastal GOM and CSK with different productivity and carbon fluxes. Based on our model results, the potential primary production rate in the inner (brown water) zone are over 2 gC m−2 d−1 (GOM) and 1.5 gC m−2 d−1 (CSK). In the middle (green water) zone, potential production is from 0.1 to 2 (GOM) and 0.3 to 1.5 gC m−2 d−1 (CSK). In the offshore (blue water) zone, productivity is less than 0.1 (GOM) and 0.3 (CSK) gC m−2 d−1. Through our model scenario results, overall oxygen demand in the GOM will increase approximately 21 % if we fail to reduce riverine N input, likely increasing considerably the area affected by hypoxia. Comparing the results from the USA with those from the Korean Peninsula shows the importance of considering both riverine and atmospheric inputs of nitrogen. This has direct implications for investigating how changes in energy technologies can lead to changes in the production of various atmospheric contaminants that affect air quality, climate and the health of local populations.

Correction to: Effects of New Zealand blackcurrant extract on sport climbing performance - J. A. Potter; C. I. Hodgson; M. Broadhurst; L. Howell; J. Gilbert; M. E. T. Willems; I. C. Perkins (European Journal of Applied Physiology, 2020)

Effects of New Zealand blackcurrant extract on sport climbing performance - J. A. Potter; C. I. Hodgson; M. Broadhurst; L. Howell; J. Gilbert; M. E. T. Willems; I. C. Perkins (European Journal of Applied Physiology, 2020)

Oiling of American white pelicans, common loons, and northern gannets in the winter following the Deepwater Horizon (MC252) oil spill - J. D. Paruk; I. J. Stenhouse; B. J. Sigel; E. M. Adams; W. A. Montevecchi; D. C. Evers; A. T. Gilbert; M. Duron; D. Long; J. Hemming; P. Tuttle (Environmental Monitoring and Assessment, 2019)
The Natural Resource Damage Assessment and Restoration Trustees for the Deepwater Horizon oil spill assessed the external oiling of migratory bird species dependent on open water in the Gulf of Mexico following the aforementioned spill. The assessment was designed to evaluate birds that use open water during the winter within 40 km of the Gulf shoreline. We focused on the American white pelican ( Pelecanus erythrorhynchos ), common loon ( Gavia immer ), and northern gannet ( Morus bassanus ). Point counts (pelican, loon) or strip transects (gannet) were used and each target species was assessed for oiling (unoiled, trace, light, moderate, or heavy amounts) and photographed. Due to distance at sighting and/or poor visibility, not all visible birds were assessed. The percentage of birds oiled varied by species, with the common loon being the highest (23.6%), followed by American white pelican (16.9%), and northern gannet (6.9%). Most of the American white pelicans and common loons had trace (83% and 72%, respectively) or light levels (11% and 24%, respectively) of oiling. The northern gannet had just trace levels of oiling. Some pelicans (6%) and loons (4%) had moderate amounts of oiling. Based on expert derived-mortality estimates and our estimates of oil exposure, we used Monte Carlo simulations to predict expected decreases of 2.5%, 4%, and 11% in the observed population for the northern gannet, American white pelican, and common loon, respectively. While these values are underestimates of the true values given the long time lag (10–12 months) between the oil spill and the assessment, these data represent some of the few estimates of exposure for these species and describe minimum risk estimates to these species.

The discovery of Neotropical Lepidosira (Collembola, Entomobryidae) and its systematic position - Rudy C. Nunes; Nerivânia N. Godeiro; George Pacheco; Shanlin Liu; Marcus Thomas P. Gilbert; Fernando Alvarez‐Valin; Feng Zhang; Bruno C. Bellini (Zoologica Scripta, 2019)
We herein present the first reliable record of Lepidosira from Neotropical Region. Lepidosira neotropicalis sp. n. from Brazil is described and illustrated in detail, including its complete mitochondrial genome. We perform a Bayesian phylogenetic analysis to place the new species within the Entomobryidae, and at the same time to test previous contrasting hypotheses on Lepidosira position within the Entomobryinae versus Seirinae for the first time. Phylogenetic analyses were based on one mitochondrial and two nuclear genes, Cytochrome Oxidase subunit I, 18S ribosomal RNA and 28S ribosomal RNA, respectively. Lepidosira neotropicalis sp. n. resembles L. sundana Yoshii and Suhardjono and L. nigropunctata (Nguyen) in dorsal chaetotaxy of abdominal segments I and II, but differs from all other species by the combination of head (dorsally and ventrally) and dorsal trunk chaetotaxy, plus empodial complex morphology. Our phylogenetic analyses support the placement of Lepidosira within Entomobryinae, as the sister group of Lepidocyrtoides . Overall, our revision enables a more objective diagnosis to Lepidosira and suggests that the genus is in need of a full revision due to its variable morphology, and lack of data needed to evaluate its monophyly. Finally, we provide an identification key for Neotropical genera of Entomobryinae.

Dispersal of a nearshore marine fish connects marine reserves and adjacent fished areas along an open coast - Diana S. Baetscher; Eric C. Anderson; Elizabeth A. Gilbert‐Horvath; Daniel P. Malone; Emily T. Saarman; Mark H. Carr; John Carlos Garza (Molecular Ecology, 2019)
Marine species with pelagic larvae typically exhibit little population structure, suggesting long‐distance dispersal and high gene flow. Directly quantifying dispersal of marine fishes is challenging but important, particularly for the design of marine protected areas (MPAs). Here, we studied kelp rockfish ( Sebastes atrovirens ) sampled along ~25 km of coastline in a boundary current‐dominated ecosystem and used genetic parentage analysis to identify dispersal events and characterize them, because the distance between sedentary parents and their settled offspring is the lifetime dispersal distance. Large sample sizes and intensive sampling are critical for increasing the likelihood of detecting parent–offspring matches in such systems and we sampled more than 6,000 kelp rockfish and analysed them with a powerful set of 96 microhaplotype markers. We identified eight parent–offspring pairs with high confidence, including two juvenile fish that were born inside MPAs and dispersed to areas outside MPAs, and four fish born in MPAs that dispersed to nearby MPAs. Additionally, we identified 25 full‐sibling pairs, which occurred throughout the sampling area and included all possible combinations of inferred dispersal trajectories. Intriguingly, these included two pairs of young‐of‐the‐year siblings with one member each sampled in consecutive years. These sibling pairs suggest monogamy, either intentional or accidental, which has not been previously demonstrated in rockfishes. This study provides the first direct observation of larval dispersal events in a current‐dominated ecosystem and direct evidence that larvae produced within MPAs are exported both to neighbouring MPAs and to proximate areas where harvest is allowed.

Host‐derived population genomics data provides insights into bacterial and diatom composition of the killer whale skin - Rebecca Hooper; Jaelle C. Brealey; Tom van der Valk; Antton Alberdi; John W. Durban; Holly Fearnbach; Kelly M. Robertson; Robin W. Baird; M. Bradley Hanson; Paul Wade; M. Thomas P. Gilbert; Phillip A. Morin; et al. (Molecular Ecology, 2019)
Recent exploration into the interactions and relationship between hosts and their microbiota has revealed a connection between many aspects of the host's biology, health and associated micro‐organisms. Whereas amplicon sequencing has traditionally been used to characterize the microbiome, the increasing number of published population genomics data sets offers an underexploited opportunity to study microbial profiles from the host shotgun sequencing data. Here, we use sequence data originally generated from killer whale Orcinus orca skin biopsies for population genomics, to characterize the skin microbiome and investigate how host social and geographical factors influence the microbial community composition. Having identified 845 microbial taxa from 2.4 million reads that did not map to the killer whale reference genome, we found that both ecotypic and geographical factors influence community composition of killer whale skin microbiomes. Furthermore, we uncovered key taxa that drive the microbiome community composition and showed that they are embedded in unique networks, one of which is tentatively linked to diatom presence and poor skin condition. Community composition differed between Antarctic killer whales with and without diatom coverage, suggesting that the previously reported episodic migrations of Antarctic killer whales to warmer waters associated with skin turnover may control the effects of potentially pathogenic bacteria such as Tenacibaculum dicentrarchi . Our work demonstrates the feasibility of microbiome studies from host shotgun sequencing data and highlights the importance of metagenomics in understanding the relationship between host and microbial ecology.

What are the Conditions of Riparian Ecosystems? Identifying Impaired Floodplain Ecosystems across the Western U.S. Using the Riparian Condition Assessment (RCA) Tool - William W. Macfarlane; Jordan T. Gilbert; Joshua D. Gilbert; William C. Saunders; Nate Hough-Snee; Chalese Hafen; Joseph M. Wheaton; Stephen N. Bennett (Environmental Management, 2018)

Ectopic, retroperitoneal adrenocortical carcinoma in the setting of Lynch syndrome - Jesse P. Wright; Kathleen W. Montgomery; Joshua Tierney; Jill Gilbert; Carmen C. Solórzano; Kamran Idrees (Familial Cancer, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Freedom from Tritrichomonas foetus infection in cattle in St. Kitts - Kimberly E. Coker; Joseph J. Lim; Rebecca L. Schleisman; Christopher Vosloo; Hilari M. French; Juan C. Samper; John J. Callanan; Robert O. Gilbert; Fortune Sithole; Chaoqun Yao; Aspinas Chapwanya (Tropical Animal Health and Production, 2018)

Evaluation of eDNA for groundwater invertebrate detection and monitoring: a case study with endangered Stygobromus (Amphipoda: Crangonyctidae) - Matthew L. Niemiller; Megan L. Porter; Jenna Keany; Heather Gilbert; Daniel W. Fong; David C. Culver; Christopher S. Hobson; K. Denise Kendall; Mark A. Davis; Steven J. Taylor (Conservation Genetics Resources, 2018)

Biophysical Approaches to Protein Folding and Disease, a satellite meeting to the IUPAB-EBSA congress - Mauro Dalla Serra; Robert J. C. Gilbert; André Matagne; Patrick England (European Biophysics Journal, 2018)

Developing new age-specific prostate-specific antigen thresholds for testing for prostate cancer - Rebecca Gilbert; Kate Tilling; Richard M. Martin; J. Athene Lane; Michael Davis; Freddie C. Hamdy; David E. Neal; Jenny L. Donovan; Chris Metcalfe (Cancer Causes & Control, 2018)

Early transcriptional response pathways in Daphnia magna are coordinated in networks of crustacean‐specific genes - Luisa Orsini; James B. Brown; Omid Shams Solari; Dong Li; Shan He; Ram Podicheti; Marcus H. Stoiber; Katina I. Spanier; Donald Gilbert; Mieke Jansen; Douglas B. Rusch; Michael E. Pfrender; et al. (Molecular Ecology, 2018)
Natural habitats are exposed to an increasing number of environmental stressors that cause important ecological consequences. However, the multifarious nature of environmental change, the strength and the relative timing of each stressor largely limit our understanding of biological responses to environmental change. In particular, early response to unpredictable environmental change, critical to survival and fitness in later life stages, is largely uncharacterized. Here, we characterize the early transcriptional response of the keystone species Daphnia magna to twelve environmental perturbations, including biotic and abiotic stressors. We first perform a differential expression analysis aimed at identifying differential regulation of individual genes in response to stress. This preliminary analysis revealed that a few individual genes were responsive to environmental perturbations and they were modulated in a stressor and genotype‐specific manner. Given the limited number of differentially regulated genes, we were unable to identify pathways involved in stress response. Hence, to gain a better understanding of the genetic and functional foundation of tolerance to multiple environmental stressors, we leveraged the correlative nature of networks and performed a weighted gene co‐expression network analysis. We discovered that approximately one‐third of the Daphnia genes, enriched for metabolism, cell signalling and general stress response, drives transcriptional early response to environmental stress and it is shared among genetic backgrounds. This initial response is followed by a genotype‐ and/or condition‐specific transcriptional response with a strong genotype‐by‐environment interaction. Intriguingly, genotype‐ and condition‐specific transcriptional response is found in genes not conserved beyond crustaceans, suggesting niche‐specific adaptation.

Phosphorus dynamics and phosphatase activity of soils under corn production with supplemental irrigation in humid coastal plain region, USA - Gilbert C. Sigua; Kenneth C. Stone; Philip J. Bauer; Ariel A. Szogi (Nutrient Cycling in Agroecosystems, 2017)

Post-diagnosis serum insulin-like growth factors in relation to dietary and lifestyle changes in the Prostate testing for cancer and Treatment (ProtecT) trial - Vanessa Er; Kalina Biernacka; Andrew J. Simpkin; Richard M. Martin; Mona Jeffreys; Pauline Emmett; Rebecca Gilbert; Kerry N. L. Avery; Eleanor Walsh; Michael Davis; Jenny L. Donovan; David E. Neal; et al. (Cancer Causes & Control, 2017)
Purpose The insulin-like growth factor (IGF) system is modifiable by diet and lifestyle, and has been linked to prostate cancer development and progression. Methods We conducted a prospective cohort study of 621 men diagnosed with localized prostate cancer to investigate the associations of dietary and lifestyle changes with post-diagnosis circulating levels of IGF-I and IGFBP-3. We used analysis of covariance to estimate the associations, controlling for baseline IGF-I or IGFBP-3, respectively. Results Mean IGF-I levels were 6.5% (95% CI −12.8, −0.3%, p = 0.04) lower in men who decreased their protein intake after diagnosis compared to men who did not change. Men who changed their fruit and vegetable intake had lower IGF-I levels compared to non-changers [Decreased intake: −10.1%, 95% CI −18.4, −1.8%, p = 0.02; Increased intake: −12.0%, 95% CI −18.4, −1.8%, p = 0.002]. IGFBP-3 was 14.6% (95% CI −24.5, −4.8%, p = 0.004) lower in men who achieved a healthy body mass index after diagnosis. Men who became inactive had 9.5% higher average IGF-I levels (95% CI 0.1, 18.9%, p = 0.05). Conclusions Decreased protein intake and body mass index, and increased physical activity and fruit and vegetable intake, following a prostate cancer diagnosis were associated with reduced post-diagnosis serum IGF-I and IGFBP-3. Counterintuitively, reduced fruit and vegetable intake was also associated with reduced IGF-I, but with weak statistical support, possibly implicating chance. If confirmed in other studies, our findings may inform potential lifestyle interventions in prostate cancer. ProtecT was registered at International Standard Randomised Controlled Trial Registry, http://isrctn.org as ISRCTN20141297.

Inferring infection hazard in wildlife populations by linking data across individual and population scales - Kim M. Pepin; Shannon L. Kay; Ben D. Golas; Susan S. Shriner; Amy T. Gilbert; Ryan S. Miller; Andrea L. Graham; Steven Riley; Paul C. Cross; Michael D. Samuel; Mevin B. Hooten; Jennifer A. Hoeting; et al. (Ecology Letters, 2017)
Our ability to infer unobservable disease‐dynamic processes such as force of infection (infection hazard for susceptible hosts) has transformed our understanding of disease transmission mechanisms and capacity to predict disease dynamics. Conventional methods for inferring FOI estimate a time‐averaged value and are based on population‐level processes. Because many pathogens exhibit epidemic cycling and FOI is the result of processes acting across the scales of individuals and populations, a flexible framework that extends to epidemic dynamics and links within‐host processes to FOI is needed. Specifically, within‐host antibody kinetics in wildlife hosts can be short‐lived and produce patterns that are repeatable across individuals, suggesting individual‐level antibody concentrations could be used to infer time since infection and hence FOI . Using simulations and case studies (influenza A in lesser snow geese and Yersinia pestis in coyotes), we argue that with careful experimental and surveillance design, the population‐level FOI signal can be recovered from individual‐level antibody kinetics, despite substantial individual‐level variation. In addition to improving inference, the cross‐scale quantitative antibody approach we describe can reveal insights into drivers of individual‐based variation in disease response, and the role of poorly understood processes such as secondary infections, in population‐level dynamics of disease.

Hong Kong’s rich marine biodiversity: the unseen wealth of South China’s megalopolis - Terence P. T. Ng; Martin C. F. Cheng; Kevin K. Y. Ho; Gilbert C. S. Lui; Kenneth M. Y. Leung; Gray A. Williams (Biodiversity and Conservation, 2017)

Drivers of density for the exploited giant clam Tridacna maxima : a meta‐analysis - Simon Van Wynsberge; Serge Andréfouët; Nabila Gaertner‐Mazouni; Colette C C Wabnitz; Antoine Gilbert; Georges Remoissenet; Claude Payri; Cécile Fauvelot (Fish and Fisheries, 2016)
Giant clam populations have been over‐exploited throughout their range over the past decades for their meat and shells. Tridacna maxima, commonly known as the ‘small giant clam’, has remained relatively untargeted by fishers in areas where larger species occur (e.g. Tridacna squamosa ), and high densities of the species are still observed on some isolated and enclosed reefs of the Central Pacific. However, it is unclear whether reported discrepancies in densities worldwide reflect differences in fishing pressure only or a combination of differences in exploitation levels and environmental forcing. We reviewed T. maxima surveys throughout its range to (i) identify patterns of density at global scale, site scale (e.g. island) and intrasite scale; (ii) discuss the influence of sampling method on density estimates; and (iii) identify the primary drivers of giant clam density along gradients of human pressure and natural forcing. We found 59 studies that reported density estimates for 172 sites across 26 countries in the Indo‐Pacific and Red Sea. At intrasite scale, densities were strongly dependent on sampling protocols and surveyed habitats. At site scale, we found close links between T. maxima density and human population per reef area, suggesting that isolated reefs where exploitation only recently started may be more vulnerable to stock collapse in the future. Density patterns were also found to vary significantly depending on reef type (e.g. atoll, island, continental coastline). We discuss how natural processes and fishing pressure may control population dynamics and densities among sites, and make recommendations for future research.

Measuring kinetic drivers of pneumolysin pore structure - Robert J. C. Gilbert; Andreas F.-P. Sonnen (European Biophysics Journal, 2016)

Remembering Jerry Lwanga: A Perspective from His Colleagues - Tony L. Goldberg; Samuel Angedakin; Gilbert M. Isabirye Basuta; Michelle Brown; Thomas M. Butynski; Colin A. Chapman; Lauren Chapman; Sholly Gunter; Innocent Kato; Jean-Michel Krief; Sabrina Krief; Joanna E. Lambert; et al. (International Journal of Primatology, 2016)

The communication, development, and promotion of biophysical science in a European and international context - Robert J. C. Gilbert (European Biophysics Journal, 2016)

Seed-Specific Stable Expression of the α-AI1 Inhibitor in Coffee Grains and the In Vivo Implications for the Development of the Coffee Berry Borer - Érika V. S. Albuquerque; Caroline A. Bezerra; Juan V. Romero; Jorge W. A. Valencia; Arnubio Valencia-Jiménez; Lucas M. Pimenta; Aulus E. A. D. Barbosa; Maria C. M. Silva; Ana M. Meneguim; Maria Eugênia L. Sá; Gilbert Engler; Janice de Almeida-Engler; et al. (Tropical Plant Biology, 2015)

Preparation of legionaminic acid analogs of sialo-glycoconjugates by means of mammalian sialyltransferases - David C. Watson; Warren W. Wakarchuk; Christian Gervais; Yves Durocher; Anna Robotham; Steve M. Fernandes; Ronald L. Schnaar; N. Martin Young; Michel Gilbert (Glycoconjugate Journal, 2015)

Undetected Blooms in Prince William Sound: Using Multiple Techniques to Elucidate the Base of the Summer Food Web - Allison S. McInnes; Clifton C. Nunnally; Gilbert T. Rowe; Randall W. Davis; Antonietta Quigg (Estuaries and Coasts, 2015)

Geographic and temporal dynamics of a global radiation and diversification in the killer whale - Phillip A. Morin; Kim M. Parsons; Frederick I. Archer; María C. Ávila‐Arcos; Lance G. Barrett‐Lennard; Luciano Dalla Rosa; Sebastián Duchêne; John W. Durban; Graeme M. Ellis; Steven H. Ferguson; John K. Ford; Michael J. Ford; et al. (Molecular Ecology, 2015)
Global climate change during the Late Pleistocene periodically encroached and then released habitat during the glacial cycles, causing range expansions and contractions in some species. These dynamics have played a major role in geographic radiations, diversification and speciation. We investigate these dynamics in the most widely distributed of marine mammals, the killer whale ( Orcinus orca ), using a global data set of over 450 samples. This marine top predator inhabits coastal and pelagic ecosystems ranging from the ice edge to the tropics, often exhibiting ecological, behavioural and morphological variation suggestive of local adaptation accompanied by reproductive isolation. Results suggest a rapid global radiation occurred over the last 350 000 years. Based on habitat models, we estimated there was only a 15% global contraction of core suitable habitat during the last glacial maximum, and the resources appeared to sustain a constant global effective female population size throughout the Late Pleistocene. Reconstruction of the ancestral phylogeography highlighted the high mobility of this species, identifying 22 strongly supported long‐range dispersal events including interoceanic and interhemispheric movement. Despite this propensity for geographic dispersal, the increased sampling of this study uncovered very few potential examples of ancestral dispersal among ecotypes. Concordance of nuclear and mitochondrial data further confirms genetic cohesiveness, with little or no current gene flow among sympatric ecotypes. Taken as a whole, our data suggest that the glacial cycles influenced local populations in different ways, with no clear global pattern, but with secondary contact among lineages following long‐range dispersal as a potential mechanism driving ecological diversification.

The Tosontsengel Mongolia world record sea‐level pressure extreme: spatial analysis of elevation bias in adjustment‐to‐sea‐level pressures - Gomboluudev Purevjav; Robert C. Balling; Randall S. Cerveny; Rob Allan; Gilbert P. Compo; Philip Jones; Thomas C. Peterson; Manola Brunet; Fatima Driouech; José Luis Stella; Bohumil M. Svoma; Daniel Krahenbuhl; et al. (International Journal of Climatology, 2015)
A World Meteorological Organization ( WMO ) committee evaluated the record sea‐level pressure ( SLP ) measurement of 1089.4 hPa on 30 December 2004 in Tosontsengel, Mongolia (1724.6 m). Although instrumentation and data collection procedures were properly followed according to the assessment of the committee, concern was raised regarding the reliability of SLP adjustment from such a high‐elevation station. This paper addresses this concern with a number of analyses that look at relationships between SLP extremes and corresponding station elevation and temperature. First, we selected data from stations extracted from the Integrated Surface Database ( ISD ‐Lite) of NOAA 's National Climate Data Center. A spatial analysis indicates that elevation shows little to no association ( R 2 values essentially zero) to extreme SLP . However, a second analysis between extreme SLP and air temperature indicates that high regionalism exists in spatial correlations (local R 2 ) between those two variables. This relationship to temperature is likely the result of differences in SLP adjustment formulae used around the world. Based on this analysis, on the need to differentiate the SLP values adjusted using extremely cold temperatures (and generally high elevation), and following past WMO SLP guidelines, the WMO Rapporteurs for Climate and Weather Extremes therefore have created two distinct SLP records: (a) highest adjusted SLP (below 750 m), currently 1083.3 hPa recorded on 31 December 1968 at Agata, Evenhiyskiy, Russia; and (b) highest adjusted SLP (above 750 m), currently 1089.4 hPa (by Russian method; 1089.1 hPa by WMO formula) on 30 December 2004 in Tosontsengel, Mongolia. Future WMO guidance regarding SLP adjustment may lead to re‐evaluation of this and other SLP records.

Comment to “Primates in the Eocene” by Gingerich (2012) - Christopher C. Gilbert; Stephanie A. Maiolino (Palaeobiodiversity and Palaeoenvironments, 2015)

An example of enhanced tephra deposition driven by topographically induced atmospheric turbulence - Sebastian F. L. Watt; Jennie S. Gilbert; Arnau Folch; Jeremy C. Phillips; Xiaoming M. Cai (Bulletin of Volcanology, 2015)

Severity markers in severe leptospirosis: a cohort study - M. Mikulski; P. Boisier; F. Lacassin; M.-E. Soupé-Gilbert; C. Mauron; L. Bruyere-Ostells; D. Bonte; Y. Barguil; A.-C. Gourinat; M. Matsui; F. Vernel-Pauillac; C. Goarant (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Disturbed subsurface microbial communities follow equivalent trajectories despite different structural starting points - Kim M. Handley; Kelly C. Wrighton; Christopher S. Miller; Michael J. Wilkins; Rose S. Kantor; Brian C. Thomas; Kenneth H. Williams; Jack A. Gilbert; Philip E. Long; Jillian F. Banfield (Environmental Microbiology, 2015)
Summary Microbial community structure, and niche and neutral processes can all influence response to disturbance. Here, we provide experimental evidence for niche versus neutral and founding community effects during a bioremediation‐related organic carbon disturbance. Subsurface sediment, partitioned into 22 flow‐through columns, was stimulated in situ by the addition of acetate as a carbon and electron donor source. This drove the system into a new transient biogeochemical state characterized by iron reduction and enriched D esulfuromonadales , C omamonadaceae and B acteroidetes lineages. After approximately 1 month conditions favoured sulfate reduction, and were accompanied by a substantial increase in the relative abundance of D esulfobulbus , D esulfosporosinus , D esulfitobacterium and D esulfotomaculum . Two subsets of four to five columns each were switched from acetate to lactate amendment during either iron (earlier) or sulfate (later) reduction. Hence, subsets had significantly different founding communities. All lactate treatments exhibited lower relative abundances of D esulfotomaculum and B acteroidetes , enrichments of C lostridiales and P sychrosinus species, and a temporal succession from highly abundant C lostridium sensu stricto to P sychrosinus . Regardless of starting point, lactate‐switch communities followed comparable structural trajectories, whereby convergence was evident 9 to 16 days after each switch, and significant after 29 to 34 days of lactate addition. Results imply that neither the founding community nor neutral processes influenced succession following perturbation.

Associations of vitamin D pathway genes with circulating 25-hydroxyvitamin-D, 1,25-dihydroxyvitamin-D, and prostate cancer: a nested case–control study - Rebecca Gilbert; Carolina Bonilla; Chris Metcalfe; Sarah Lewis; David M. Evans; William D. Fraser; John P. Kemp; Jenny L. Donovan; Freddie C. Hamdy; David E. Neal; J. Athene Lane; George Davey Smith; et al. (Cancer Causes & Control, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Transcriptomic profiling facilitates classification of response to influenza challenge - Emma E. Davenport; Richard D. Antrobus; Patrick J. Lillie; Sarah Gilbert; Julian C. Knight (Journal of Molecular Medicine, 2015)

Diet and Phylogeny in Primate Communities - Leila M. Porter; Christopher C. Gilbert; John G. Fleagle (International Journal of Primatology, 2014)

Male Scudderia pistillata katydids defend their acoustic duet against eavesdroppers - S. M. Villarreal; C. Gilbert (Behavioral Ecology and Sociobiology, 2014)

Stratigraphic status, age, and paleobathymetry of the Grey shale Member, Dalmiapuram Formation, Cauvery Basin, India - R. Nagendra; P. Sathiyamoorthy; A. N. Reddy; Harry Gilbert; B. C. Jaiprakash (Arabian Journal of Geosciences, 2014)

Striatal patch compartment lesions alter methamphetamine-induced behavior and immediate early gene expression in the striatum, substantia nigra and frontal cortex - Ryan C. Murray; Yamiece E. Gilbert; Anna S. Logan; John C. Hebbard; Kristen A. Horner (Brain Structure and Function, 2014)

Gain-of-function mutation in Gnao1: A murine model of epileptiform encephalopathy (EIEE17)? - Jason M. Kehrl; Kinshuk Sahaya; Hans M. Dalton; Raelene A. Charbeneau; Kevin T. Kohut; Kristen Gilbert; Madeline C. Pelz; Jack Parent; Richard R. Neubig (Mammalian Genome, 2014)
G protein-coupled receptors strongly modulate neuronal excitability but there has been little evidence for G protein mechanisms in genetic epilepsies. Recently, four patients with epileptic encephalopathy (EIEE17) were found to have mutations in GNAO1, the most abundant G protein in brain, but the mechanism of this effect is not known. The GNAO1 gene product, Gα o , negatively regulates neurotransmitter release. Here, we report a dominant murine model of Gnao1 -related seizures and sudden death. We introduced a genomic gain-of-function knock-in mutation ( Gnao1 +/G184S ) that prevents G o turnoff by Regulators of G protein signaling proteins. This results in rare seizures, strain-dependent death between 15 and 40 weeks of age, and a markedly increased frequency of interictal epileptiform discharges. Mutants on a C57BL/6J background also have faster sensitization to pentylenetetrazol (PTZ) kindling. Both premature lethality and PTZ kindling effects are suppressed in the 129SvJ mouse strain. We have mapped a 129S-derived modifier locus on Chromosome 17 (within the region 41–70 MB) as a Modifer of G protein Seizures ( Mogs1 ). Our mouse model suggests a novel gain-of-function mechanism for the newly defined subset of epileptic encephalopathy (EIEE17). Furthermore, it reveals a new epilepsy susceptibility modifier Mogs1 with implications for the complex genetics of human epilepsy as well as sudden death in epilepsy.

Dynamic recruitment of amino acid transporters to the insect/symbiont interface - Rebecca P. Duncan; Filip Husnik; James T. Van Leuven; Donald G. Gilbert; Liliana M. Dávalos; John P. McCutcheon; Alex C. C. Wilson (Molecular Ecology, 2014)
Symbiosis is well known to influence bacterial symbiont genome evolution and has recently been shown to shape eukaryotic host genomes. Intriguing patterns of host genome evolution, including remarkable numbers of gene duplications, have been observed in the pea aphid, a sap‐feeding insect that relies on a bacterial endosymbiont for amino acid provisioning. Previously, we proposed that gene duplication has been important for the evolution of symbiosis based on aphid‐specific gene duplication in amino acid transporters ( AAT s), with some paralogs highly expressed in the cells housing symbionts (bacteriocytes). Here, we use a comparative approach to test the role of gene duplication in enabling recruitment of AAT s to bacteriocytes. Using genomic and transcriptomic data, we annotate AAT s from sap‐feeding and non sap‐feeding insects and find that, like aphids, AAT gene families have undergone independent large‐scale gene duplications in three of four additional sap‐feeding insects. RNA ‐seq differential expression data indicate that, like aphids, the sap‐feeding citrus mealybug possesses several lineage‐specific bacteriocyte‐enriched paralogs. Further, differential expression data combined with quantitative PCR support independent evolution of bacteriocyte enrichment in sap‐feeding insect AAT s. Although these data indicate that gene duplication is not necessary to initiate host/symbiont amino acid exchange, they support a role for gene duplication in enabling AAT s to mediate novel host/symbiont interactions broadly in the sap‐feeding suborder Sternorrhyncha. In combination with recent studies on other symbiotic systems, gene duplication is emerging as a general pattern in host genome evolution.

Groundwater phosphorus in forage-based landscape with cow-calf operation - Gilbert C. Sigua; Chad C. Chase (Environmental Monitoring and Assessment, 2014)

Soil-extractable phosphorus and phosphorus saturation threshold in beef cattle pastures as affected by grazing management and forage type - Gilbert C. Sigua; Chad C. Chase; Joseph Albano (Environmental Science and Pollution Research, 2014)

Phytoremediation of Pb in the sediment of a mangrove ecosystem - Annie Melinda Paz-Alberto; Arnel B. Celestino; Gilbert C. Sigua (Journal of Soils and Sediments, 2014)

Genome-wide association study and meta-analysis of intraocular pressure - A. Bilge Ozel; Sayoko E. Moroi; David M. Reed; Melisa Nika; Caroline M. Schmidt; Sara Akbari; Kathleen Scott; Frank Rozsa; Hemant Pawar; David C. Musch; Paul R. Lichter; Doug Gaasterland; et al. (Human Genetics, 2014)

Deriving field-based sediment quality guidelines from the relationship between species density and contaminant level using a novel nonparametric empirical Bayesian approach - Gilbert C. S. Lui; W. K. Li; Anders Bjørgesæter; Kenneth M. Y. Leung (Environmental Science and Pollution Research, 2014)

Are HPV vaccination services accessible to high-risk communities? A spatial analysis of HPV-associated cancer and Chlamydia rates and safety-net clinics - Jennifer Tsui; Hector P. Rodriguez; Gilbert C. Gee; Loraine A. Escobedo; Gerald F. Kominski; Roshan Bastani (Cancer Causes & Control, 2013)

Mitogenomic insights into a recently described and rarely observed killer whale morphotype - Andrew D. Foote; Phillip A. Morin; Robert L. Pitman; María C. Ávila-Arcos; John W. Durban; Anton van Helden; Mikkel-Holger S. Sinding; M. Thomas P. Gilbert (Polar Biology, 2013)

Underground signals carried through common mycelial networks warn neighbouring plants of aphid attack - Zdenka Babikova; Lucy Gilbert; Toby J. A. Bruce; Michael Birkett; John C. Caulfield; Christine Woodcock; John A. Pickett; David Johnson (Ecology Letters, 2013)
The roots of most land plants are colonised by mycorrhizal fungi that provide mineral nutrients in exchange for carbon. Here, we show that mycorrhizal mycelia can also act as a conduit for signalling between plants, acting as an early warning system for herbivore attack. Insect herbivory causes systemic changes in the production of plant volatiles, particularly methyl salicylate, making bean plants, Vicia faba , repellent to aphids but attractive to aphid enemies such as parasitoids. We demonstrate that these effects can also occur in aphid‐free plants but only when they are connected to aphid‐infested plants via a common mycorrhizal mycelial network. This underground messaging system allows neighbouring plants to invoke herbivore defences before attack. Our findings demonstrate that common mycorrhizal mycelial networks can determine the outcome of multitrophic interactions by communicating information on herbivore attack between plants, thereby influencing the behaviour of both herbivores and their natural enemies.

Men with prostate cancer make positive dietary changes following diagnosis and treatment - Kerry N. L. Avery; Jenny L. Donovan; Rebecca Gilbert; Michael Davis; Pauline Emmett; Liz Down; Steven Oliver; David E. Neal; Freddie C. Hamdy; J. Athene Lane (Cancer Causes & Control, 2013)

Corrigendum - Kimberly J. Gilbert; Rose L. Andrew; Dan G. Bock; Michelle T. Franklin; Nolan C. Kane; Jean‐Sébastien Moore; Brook T. Moyers; Sébastien Renaut; Diana J. Rennison; Thor Veen; Timothy H. Vines (Molecular Ecology, 2013)

Different responses of selected hormones to three types of exercise in young men - Keith A. Stokes; Kate L. Gilbert; George M. Hall; Robert C. Andrews; Dylan Thompson (European Journal of Applied Physiology, 2013)

Recommendations for utilizing and reporting population genetic analyses: the reproducibility of genetic clustering using the program structure - Kimberly J. Gilbert; Rose L. Andrew; Dan G. Bock; Michelle T. Franklin; Nolan C. Kane; Jean‐Sébastien Moore; Brook T. Moyers; Sébastien Renaut; Diana J. Rennison; Thor Veen; Timothy H. Vines (Molecular Ecology, 2012)
Reproducibility is the benchmark for results and conclusions drawn from scientific studies, but systematic studies on the reproducibility of scientific results are surprisingly rare. Moreover, many modern statistical methods make use of ‘random walk’ model fitting procedures, and these are inherently stochastic in their output. Does the combination of these statistical procedures and current standards of data archiving and method reporting permit the reproduction of the authors' results? To test this, we reanalysed data sets gathered from papers using the software package structure to identify genetically similar clusters of individuals. We find that reproducing structure results can be difficult despite the straightforward requirements of the program. Our results indicate that 30% of analyses were unable to reproduce the same number of population clusters. To improve this, we make recommendations for future use of the software and for reporting structure analyses and results in published works.

Mind the gap: a comparative study of migratory behavior in social amoebae - Owen M. Gilbert; Jennie J. Kuzdzal-Fick; David C. Queller; Joan E. Strassmann (Behavioral Ecology and Sociobiology, 2012)

DNA from soil mirrors plant taxonomic and growth form diversity - N. G. YOCCOZ; K. A. BRÅTHEN; L. GIELLY; J. HAILE; M. E. EDWARDS; T. GOSLAR; H. Von STEDINGK; A. K. BRYSTING; E. COISSAC; F. POMPANON; J. H. SØNSTEBØ; C. MIQUEL; et al. (Molecular Ecology, 2012)
Ecosystems across the globe are threatened by climate change and human activities. New rapid survey approaches for monitoring biodiversity would greatly advance assessment and understanding of these threats. Taking advantage of next‐generation DNA sequencing, we tested an approach we call metabarcoding: high‐throughput and simultaneous taxa identification based on a very short (usually

A cross-sectional analysis of the association between diet and insulin-like growth factor (IGF)-I, IGF-II, IGF-binding protein (IGFBP)-2, and IGFBP-3 in men in the United Kingdom - Nicholas J. Young; Chris Metcalfe; David Gunnell; Mari-Anne Rowlands; J. Athene Lane; Rebecca Gilbert; Kerry N. L. Avery; Michael Davis; David E. Neal; Freddie C. Hamdy; Jenny Donovan; Richard M. Martin; et al. (Cancer Causes & Control, 2012)

Lemming winter habitat choice: a snow-fencing experiment - Donald G. Reid; Frédéric Bilodeau; Charles J. Krebs; Gilles Gauthier; Alice J. Kenney; B. Scott Gilbert; Maria C.-Y. Leung; David Duchesne; Elizabeth Hofer (Oecologia, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Mind the gap: the ratio of yolk androgens and antioxidants varies between sons and daughters dependent on paternal attractiveness - E. C. Pariser; L. Gilbert; N. Hazon; K. E. Arnold; J. A. Graves (Behavioral Ecology and Sociobiology, 2012)

Mitochondrial Haplogroup X is associated with successful aging in the Amish - Monique D. Courtenay; John R. Gilbert; Lan Jiang; Anna C. Cummings; Paul J. Gallins; Laura Caywood; Lori Reinhart-Mercer; Denise Fuzzell; Claire Knebusch; Renee Laux; Jacob L. McCauley; Charles E. Jackson; et al. (Human Genetics, 2012)

Assessing phytoremediation potentials of selected tropical plants for acrylamide - Annie Melinda Paz-Alberto; Ma. Johanna J. De Dios; Ronaldo T. Alberto; Gilbert C. Sigua (Journal of Soils and Sediments, 2011)

Spatial gradients of methylmercury for breeding common loons in the Laurentian Great Lakes region - David C. Evers; Kathryn A. Williams; Michael W. Meyer; Anton M. Scheuhammer; Nina Schoch; Andrew T. Gilbert; Lori Siegel; Robert J. Taylor; Robert Poppenga; Christopher R. Perkins (Ecotoxicology, 2011)

Erratum to: Translational Biomarkers: from Preclinical to Clinical a Report of 2009 AAPS/ACCP Biomarker Workshop - Jane P. F. Bai; Robert Bell; ShaAvhree Buckman; Gilbert J. Burckart; Hans-Georg Eichler; Kenneth C. Fang; Federico M. Goodsaid; William J. Jusko; Lawrence L. Lesko; Bernd Meibohm; Scott D. Patterson; Oscar Puig; et al. (The AAPS Journal, 2011)

Translational Biomarkers: from Preclinical to Clinical a Report of 2009 AAPS/ACCP Biomarker Workshop - Jane P. F. Bai; Robert Bell; ShaAvhree Buckman; Gilbert J. Burckart; Hans-Georg Eichler; Kenneth C. Fang; Federico M. Goodsaid; William J. Jusko; Lawrence L. Lesko; Bernd Meibohm; Scott D. Patterson; Oscar Puig; et al. (The AAPS Journal, 2011)

The combined effect of waterlogging, extractable P and soil pH on α-diversity: a case study on mesotrophic grasslands in the UK - Dana Michalcová; Joanne C. Gilbert; Clare S. Lawson; David J. G. Gowing; Rob H. Marrs (Plant Ecology, 2011)

Daphnia–rotifer interactions in Patagonian communities - María C. Diéguez; John J. Gilbert (Hydrobiologia, 2011)

Associations of circulating and dietary vitamin D with prostate cancer risk: a systematic review and dose–response meta-analysis - Rebecca Gilbert; Richard M. Martin; Rebecca Beynon; Ross Harris; Jelena Savovic; Luisa Zuccolo; Geertruida E. Bekkering; William D. Fraser; Jonathan A. C. Sterne; Chris Metcalfe (Cancer Causes & Control, 2011)

The control of marine biofouling on xerogel surfaces with nanometer-scale topography - Nikhil Gunari; Lenora H. Brewer; Stephanie M. Bennett; Anastasiya Sokolova; Nadine D. Kraut; John A. Finlay; Anne E. Meyer; Gilbert C. Walker; Dean E. Wendt; Maureen E. Callow; James A. Callow; Frank V. Bright; et al. (Biofouling, 2011)

Spatial distribution of soil phosphorus and herbage mass in beef cattle pastures: effects of slope aspect and slope position - Gilbert C. Sigua; Samuel W. Coleman; Joseph Albano; Mimi Williams (Nutrient Cycling in Agroecosystems, 2011)

Accumulation Capacities of Particulate Matter in an Acrocarpous and a Pleurocarpous Moss Exposed at Three Differently Polluted Sites (Industrial, Urban and Rural) - J. Fabure; C. Meyer; F. Denayer; A. Gaudry; D. Gilbert; N. Bernard (Water, Air, & Soil Pollution, 2010)

Erratum to: Resolving Myoarchitectural Disarray in the Mouse Ventricular Wall with Diffusion Spectrum Magnetic Resonance Imaging - Teresa T. Wang; Hyuk Sang Kwon; Guangping Dai; Ruopeng Wang; Srboljub M. Mijailovich; Richard L. Moss; Peter T. C. So; Van J. Wedeen; Richard J. Gilbert (Annals of Biomedical Engineering, 2010)

Resolving Myoarchitectural Disarray in the Mouse Ventricular Wall with Diffusion Spectrum Magnetic Resonance Imaging - Teresa T. Wang; Hyuk Sang Kwon; Guangping Dai; Ruopeng Wang; Srboljub M. Mijailovich; Richard L. Moss; Peter T. C. So; Van J. Wedeen; Richard J. Gilbert (Annals of Biomedical Engineering, 2010)

Barnacle settlement and the adhesion of protein and diatom microfouling to xerogel films with varying surface energy and water wettability - John A. Finlay; Stephanie M. Bennett; Lenora H. Brewer; Anastasiya Sokolova; Gemma Clay; Nikhil Gunari; Anne E. Meyer; Gilbert C. Walker; Dean E. Wendt; Maureen E. Callow; James A. Callow; Michael R. Detty (Biofouling, 2010)

Microbiological Quality Assessment of Watershed Associated with Animal-Based Agriculture in Santa Catarina, Brazil - Gilbert C. Sigua; Julio Cesar Pascale Palhares; Jalusa Deon Kich; Magda Regina Mulinari; Rosemari Martini Mattei; Jaqueline Bianca Klein; Susana Muller; Gustavo Plieske (Water, Air, & Soil Pollution, 2010)

Nitrogen in soils, plants, surface water and shallow groundwater in a bahiagrass pasture of Southern Florida, USA - Gilbert C. Sigua; Robert K. Hubbard; Samuel W. Coleman; Mimi Williams (Nutrient Cycling in Agroecosystems, 2010)

Spatial distribution of soil carbon in pastures with cow-calf operation: effects of slope aspect and slope position - Gilbert C. Sigua; Samuel W. Coleman (Journal of Soils and Sediments, 2010)

Quantifying phosphorus levels in soils, plants, surface water, and shallow groundwater associated with bahiagrass-based pastures - Gilbert C. Sigua; Robert K. Hubbard; Samuel W. Coleman (Environmental Science and Pollution Research, 2010)

The role of surface energy and water wettability in aminoalkyl/fluorocarbon/hydrocarbon-modified xerogel surfaces in the control of marine biofouling - Stephanie M. Bennett; John A. Finlay; Nikhil Gunari; David D. Wells; Anne E. Meyer; Gilbert C. Walker; Maureen E. Callow; James A. Callow; Frank V. Bright; Michael R. Detty (Biofouling, 2009)

Quantifying soil organic carbon in forage-based cow–calf congregation-grazing zone interface - Gilbert C. Sigua; Samuel W. Coleman; Joseph P. Albano (Nutrient Cycling in Agroecosystems, 2009)

NOS2A, TLR4, and IFNGR1 interactions influence pulmonary tuberculosis susceptibility in African-Americans - Digna Rosa Velez; William F. Hulme; Jamie L. Myers; J. Brice Weinberg; Marc C. Levesque; Martin E. Stryjewski; Eduardo Abbate; Rosa Estevan; Sara G. Patillo; John R. Gilbert; Carol D. Hamilton; William K. Scott (Human Genetics, 2009)

Discovery of a large clonal patch of a social amoeba: implications for social evolution - OWEN M GILBERT; DAVID C QUELLER; JOAN E STRASSMANN (Molecular Ecology, 2009)
Studies of genetic population structures of clonally reproducing macro‐organisms have revealed large areas where only one clone is found. These areas, referred to as clonal patches, have not been shown to occur in free‐living microbes until now. In free‐living microbes, high genetic diversity at local scales is usually maintained by high rates of dispersal. We report, however, a highly dense, 12‐m clonal patch of the social amoeba Dictyostelium discoideum in a cattle pasture located in a Texas Gulf Coast prairie. We confirm the presence of only one clone by the analysis of 65 samples and amplification of 10 polymorphic microsatellite loci. Samplings of additional cattle pastures nearby showed higher clonal diversity, but with a density of D. discoideum isolates lower than in the clonal patch. These findings show that high rates of microbial dispersal do not always produce genetic diversity at local scales, contrary to the findings of previous studies. The existence of clonal patches may be particularly important for microbial social evolution.

Nanoscale structures and mechanics of barnacle cement - Ruby May A. Sullan; Nikhil Gunari; Adrienne E. Tanur; Yuri Chan; Gary H. Dickinson; Beatriz Orihuela; Dan Rittschof; Gilbert C. Walker (Biofouling, 2009)

Within-year differences in reproductive investment in laboratory zebra finches (Taeniopygia guttata), an opportunistically breeding bird - Kathryn Williamson; Lucy Gilbert; Alison N. Rutstein; Emma C. Pariser; Jeff A. Graves (The Science of Nature, 2008)

Kriging analysis of soil properties - Gilbert C. Sigua; Wayne H. Hudnall (Journal of Soils and Sediments, 2008)

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

Chromosomal evolution in tenrecs (Microgale and Oryzorictes, Tenrecidae) from the Central Highlands of Madagascar - C. Gilbert; S. M. Goodman; V. Soarimalala; L. E. Olson; P. C. M. O’Brien; F. F. B. Elder; F. Yang; M. A. Ferguson-Smith; T. J. Robinson (Chromosome Research, 2007)

Multiple paternity in viviparous kelp rockfish, Sebastes atrovirens - Susan M. Sogard; Elizabeth Gilbert-Horvath; Eric C. Anderson; Rebecca Fisher; Steven A. Berkeley; J. Carlos Garza (Environmental Biology of Fishes, 2007)

Phytoremediation potentials of selected tropical plants for Ethidium bromide - Raynato B. Uera; Annie Melinda Paz-Alberto; Gilbert C. Sigua (Environmental Science and Pollution Research, 2007)

Phytoextraction of lead-contaminated soil using vetivergrass (Vetiveria zizanioides L.), cogongrass (Imperata cylindrica L.) and carabaograss (Paspalum conjugatum L.) - Annie Melinda Paz-Alberto; Gilbert C. Sigua; Bellrose G. Baui; Jacqueline A. Prudente (Environmental Science and Pollution Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

The phylogeny of the austral grass subfamily Danthonioideae: Evidence from multiple data sets - N. P. Barker; C. Galley; G. A. Verboom; P. Mafa; M. Gilbert; H. P. Linder (Plant Systematics and Evolution, 2007)

Chromosome painting and molecular dating indicate a low rate of chromosomal evolution in golden moles (Mammalia, Chrysochloridae) - C. Gilbert; P. C. O’Brien; G. Bronner; F. Yang; A. Hassanin; M. A. Ferguson-Smith; T. J. Robinson (Chromosome Research, 2006)

Protocols for estimating magnitudes and values of paddy rice multiple functions - Gilbert Levine; Chih-Hung Tan; Yutaka Matsuno; C.-C. Huang; Randolph Barker (Paddy and Water Environment, 2006)

Corticosteroids in patients with antiovarian antibodies undergoing in vitro fertilization: a prospective pilot study - Thierry Forges; Patricia Monnier-Barbarino; Frédérique Guillet-May; Gilbert C. Faure; Marie-Christine Béné (European Journal of Clinical Pharmacology, 2006)

Pharmacologic and Pharmacokinetic Assessment of Anti-TGFβ2 Aptamers in Rabbit Plasma and Aqueous Humor - Thomas G. McCauley; Jeffrey C. Kurz; Patricia G. Merlino; Scott D. Lewis; Madaline Gilbert; David M. Epstein; H. Nicholas Marsh (Pharmaceutical Research, 2006)

Identification of a locus for nongoitrous congenital hypothyroidism on chromosome 15q25.3-26.1 - Helmut Grasberger; Martine Vaxillaire; Silvana Pannain; John C. Beck; Aviva Mimouni-Bloch; Vincent Vatin; Gilbert Vassart; Philippe Froguel; Samuel Refetoff (Human Genetics, 2005)

Maternal mosaicism for mutations in the ARX gene in a family with X linked mental retardation - K. Poirier; J. Abriol; I. Souville; C. Laroche-Raynaud; C. Beldjord; B. Gilbert; J. Chelly; T. Bienvenu (Human Genetics, 2005)

Extraordinarily high giant clam density under protection in Tatakoto atoll (Eastern Tuamotu archipelago, French Polynesia) - A. Gilbert; L. Yan; G. Remoissenet; S. Andréfouët; C. Payri; Y. Chancerelle (Coral Reefs, 2005)

Differentially expressed genes associated with dormancy or germination of Arabidopsis thaliana seeds - Peter E. Toorop; Rosa Maria Barroco; Gilbert Engler; Steven P. C. Groot; Henk W. M. Hilhorst (Planta, 2005)

SNPs in the neural cell adhesion molecule 1 gene (NCAM1) may be associated with human neural tube defects - Kristen L. Deak; Abee L. Boyles; Heather C. Etchevers; Elizabeth C. Melvin; Deborah G. Siegel; Felicia L. Graham; Susan H. Slifer; David S. Enterline; Timothy M. George; Michel Vekemans; David McClay; Alexander G. Bassuk; et al. (Human Genetics, 2005)

Catchment–coastal zone interaction based upon scenario and model analysis: Elbe and the German Bight case study - J. Hofmann; H. Behrendt; A. Gilbert; R. Janssen; A. Kannen; J. Kappenberg; H. Lenhart; W. Lise; C. Nunneri; W. Windhorst (Regional Environmental Change, 2005)

Disruption of masking by hypothalamic lesions in Syrian hamsters - Xiaodong Li; Jenifer Gilbert; Fred C. Davis (Journal of Comparative Physiology A, 2005)

Assessing the efficacy of dredged materials from lake panasoffkee, Florida: Implication to environment and agriculture - Gilbert C. Sigua; Mike L. Holtkamp; Samuel W. Coleman (Environmental Science and Pollution Research, 2004)

Blockade of mesolimbic dopamine D3 receptors inhibits stress-induced reinstatement of cocaine-seeking in rats - Zheng-Xiong Xi; Jeremy Gilbert; Arlene C. Campos; Nicole Kline; Charles R. Ashby; Jim J. Hagan; Christian A. Heidbreder; Eliot L. Gardner (Psychopharmacology, 2004)

Assessing the efficacy of dredged materials from lake panasoffkee, florida: Implication to environment and agriculture part 1: Soil and environmental quality aspect - Gilbert C. Sigua; Mike L. Holtkamp; Samuel W. Coleman (Environmental Science and Pollution Research, 2004)

Wetland conversion to beef cattle pasture changes in soil properties - Gilbert C. Sigua; Jim Griffin; Woo-jun Kang; Samuel W. Coleman (Journal of Soils and Sediments, 2004)

Soils and environment of grazed pasture ecosystems in subtropical United States - Gilbert C. Sigua (Journal of Soils and Sediments, 2003)

Species Richness and Invasion Vectors: Sampling Techniques and Biases - S. Gollasch; H. Rosenthal; H. Botnen; M. Crncevic; M. Gilbert; J. Hamer; N. Hülsmann; C. Mauro; L. McCann; D. Minchin; B. Öztürk; M. Robertson; et al. (Biological Invasions, 2003)

Land Application of Lake-Dredged Materials for Bahiagrass Establishment in the Subtropical Beef Pasture - Gilbert C. Sigua; Mike L. Holtkamp; John M. Linton; Samuel W. Coleman (Journal of Soils and Sediments, 2003)

Lung Deposition and Pharmacokinetics of Cyclosporine After Aerosolization in Lung Transplant Patients - Gilbert J. Burckart; Gerald C. Smaldone; Michael A. Eldon; Raman Venkataramanan; James Dauber; Adriana Zeevi; Kenneth McCurry; Teresa P. McKaveney; Timothy E. Corcoran; Bartley P. Griffith; Aldo T. Iacono (Pharmaceutical Research, 2003)

Characterization of β‐haemolytic Group B Streptococcus agalactiae in cultured seabream, Sparus auratus L., and wild mullet, Liza klunzingeri (Day), in Kuwait - J J Evans; P H Klesius; P M Gilbert; C A Shoemaker; M A Al Sarawi; J Landsberg; R Duremdez; A Al Marzouk; S Al Zenki (Journal of Fish Diseases, 2002)
Streptococcus agalactiae was isolated from cultured gilthead seabream, Sparus auratus L., and diseased wild Klunzinger's mullet, Liza klunzingeri (Day), in Kuwait Bay, Arabian Gulf. Isolates were catalase negative, β‐haemolytic, Gram‐positive cocci and serogroup B. Experimental infectivity trials with mullet and seabream brain isolates in Nile tilapia, Oreochromis niloticus L., caused 100 and 90% mortality, respectively, within 7 days post‐inoculation indicating virulent S. agalactiae as the bacterial pathogen responsible for the epizootic in Kuwait Bay.

Sustainable management of transboundary river basins: a line of reasoning - Lorenz C.; Gilbert A.; Vellinga P. (Regional Environmental Change, 2001)

Spatial Economic–Hydroecological Modelling and Evaluation of Land Use Impacts in the Vecht Wetlands Area - J. van den Bergh; A. Barendregt; A. Gilbert; M. van Herwijnen; P. van Horssen; P. Kandelaars; C. Lorenz (Environmental Modeling & Assessment, 2001)

Absence of anti-hepatitis B surface antibody after vaccination does not necessarily mean absence of immune response - Gilbert Greub; Frédéric Zysset; Blaise Genton; François Spertini; Philippe C. Frei (Medical Microbiology and Immunology, 2001)

Elevational distribution of restricted range forest tree taxa in eastern Tanzania - Jon C. Lovett; G. Philip Clarke; Robin Moore; Gilbert H. Morrey (Biodiversity and Conservation, 2001)

SMN gene duplication and the emergence of the SMN2 gene occurred in distinct hominids: SMN2 is unique to Homo sapiens - C. Rochette; N. Gilbert; L. Simard (Human Genetics, 2001)

The effect of fenofibrate treatment on endothelium-dependent relaxation induced by oxidative modified low density lipoprotein from hyperlipidemic patients - Binhua Liang; Jason C. McMaster; Edwin A. Kroeger; Grant M. Hatch; David Mymin; Tom Dembinski; Gilbert Arthur; Garry Shen; Ricky Y.K. Man; Patrick C. Choy (Molecular and Cellular Biochemistry, 2000)

Water-Quality Monitoring and Biological Integrity Assessment in the Indian River Lagoon, Florida: Status, Trends, and Loadings (19881994) - Gilbert C. Sigua; Joel S. Steward; Wendy A. Tweedale (Environmental Management, 2000)

Summer distribution patterns of the backswimmer, Anisops wakefieldi (Hemiptera: Notonectidae), in a New Zealand pond - John J. Gilbert; Carolyn W. Burns; Caroline C. Gilbert (New Zealand Journal of Marine and Freshwater Research, 1999)
The relative abundance of different‐sized Anisops wakefieldi in a small, fishless pond was determined from sweep‐net samples taken along one open‐water and two shoreline transects at noon on two dates, and at noon and midnight on a third date. During the day, large individuals occurred only along the shore, whereas smaller ones occurred both along the shore and in open water. At night, large individuals also occurred in the open water. The diurnal size‐class segregation suggests that young individuals migrate into less preferred, open water to avoid interference and cannibalism from larger individuals. The shoreline may be preferred during the day because it provides greater food resources or a refuge from visually feeding avian predators. Laboratory experiments in containers with floating aquatic plants at one end complemented the field data. When alone, both small and large A. wakefieldi sought cover during the day and moved into open water at night. During the day, the presence of large individuals induced small ones to move into open water. The results of this study on a notonectid population are consistent with some earlier ones in demonstrating that interactions between large and small size classes may lead to pronounced spatial segregation of size classes, and show for the first time that spatial distributional patterns during the day and night may be very different.

The thrombospondin-4 gene - Gail Newton; Stanislawa Weremowicz; Cynthia C. Morton , , Nancy A.; Debra J. Gilbert; Neal G. Copeland; Jack Lawler (Mammalian Genome, 1999)

Effects of water velocity on algal carbon isotope ratios: Implications for river food web studies - Jacques C. Finlay; Mary E. Power; Gilbert Cabana (Limnology and Oceanography, 1999)
We used variation in algal d 13 C between river habitats to study the spatial scale of energy flow through river food webs. We found a strong negative relationship between herbivore d 13 C (which reflects algal d 13 C) and water velocity in three productive Northern California rivers but not in unproductive streams. The contrast among habitats suggests that water velocity affects algal d 13 C most strongly when CO2 availability is low relative to photosynthetic rates. Our results help explain the wide variation in published river biota d 13 C and show that past studies using carbon isotope analyses may have significantly underestimated the importance of algal‐derived carbon to river food webs. While flow‐related variation in d 13 C complicates this common application of carbon isotope analysis, we show that it provides a natural tracer of the flux of algal production derived from different habitats within rivers to higher trophic levels. Measurements of consumer d 13 C showed that most invertebrate and vertebrate consumers relied on local production, except for filter‐feeding insects and steelhead trout, which relied on production derived from multiple sources. Stable carbon isotopes may thus be used to spatially delineate the habitats that support river food webs, providing previously unavailable information for understanding and managing river ecosystems.

Identification of the key factors affecting composting of a weathered hydrocarbon-contaminated soil - A.U. Nwankwoala; N.O. Egiebor; c. Gilbert; K. Nyavor (Biodegradation, 1999)

Assessment of the Directional Elastic Moduli of Ewe Vertebral Cancellous Bone by Vibrational Testing - Paul S. Weinhold; Simon C. Roe; Jerome A. Gilbert; C. Frank Abrams (Annals of Biomedical Engineering, 1999)

Desulphurisation of benzothiophene and dibenzothiophene by actinomycete organisms belonging to the genus Rhodococcus, and related taxa - Christopher Oldfield; Nicola T. Wood; Steven C. Gilbert; Frazer D. Murray; Fabrice R. Faure (Antonie van Leeuwenhoek, 1998)

Short-term effect of nitrogen enrichment on the microbial communities of a peatland - D. Gilbert; C. Amblard; G. Bourdier; A.-J. Francez (Hydrobiologia, 1998)

Genetic mapping of the galanin-GMAP (Galn) gene to mouse Chromosome 19 - Leticia C. Guida; Philippa Charlton; Debra J. Gilbert; Nancy A. Jenkins; Neal G. Copeland; Robert D. Nicholls (Mammalian Genome, 1998)

Sur2 and Kcnj8 genes are tightly linked on the distal region of mouse Chromosome 6 - S. Isomoto; Y. Horio; S. Matsumoto; C. Kondo; M. Yamada; D.J. Gilbert; N.G. Copeland; N.A. Jenkins; Y. Kurachi (Mammalian Genome, 1997)

Wide Crosses to Improve Fusarium Blight Resistance in Wheat - George Fedak; K. C. Armstrong; R. C. Sinha; J. Gilbert; J. D. Procunier; J. D. Miller; R. Pandeya (Cereal Research Communications, 1997)

Visual control of cursorial prey pursuit by tiger beetles (Cicindelidae) - C. Gilbert (Journal of Comparative Physiology A, 1997)

cDNA cloning and chromosomal mapping of mouse fast skeletal muscle troponin T - Anne Koch; Todd S. -C. Juan; Nancy A. Jenkins; Debra J. Gilbert; Neal G. Copeland; Ian K. McNiece; Frederick A. Fletcher (Mammalian Genome, 1997)

Purification and characterization of the recombinant CMP-sialic acid synthetase from Neisseria meningitidis - Michel Gilbert; David C. Watson; Warren W. Wakarchuk (Biotechnology Letters, 1997)

Noise stress does not modulate effects of smoking/nicotine on β-endorphin, cortisol, ACTH, glucose, and mood - D. G. Gilbert; Charles J. Meliska; Louisette C. Plath (Psychopharmacology, 1997)

Effects of pentachlorophenol and other chemical preservatives on the health of wood-treating workers in Hawaii - F. I. Gilbert; C. E. Minn; R. C. Duncan; John Wilkinson (Archives of Environmental Contamination and Toxicology, 1990)

A microcomputer based controller for neuromuscular block during surgery - Gilbert Ritchie; John P. Ebert; Thomas C. Jannett; Igor Kissin; Louis C. Sheppard (Annals of Biomedical Engineering, 1985)

Nutritional and toxicological studies with growing pigs fed aquatic plant rations - Tuan N. Yap; Wilson G. Pond; Jung F. Wu; Gilbert S. Stoewsand; Patricia C. Wszolek; Donald J. Lisk (Archives of Environmental Contamination and Toxicology, 1979)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)

A role for glycine in light stimulated nucleic acid synthesis by blastocladiella emersonii - Edward C. Cantino; Gilbert Turian (Archives of Microbiology, 1961)

Identifying spindle-tuber in the field - H. O. Werner; Alfred H. Gilbert; C. L. Fitch; H. T. Güssow (American Journal of Potato Research, 1927)

Crop and market news - B. A. Brown; H. C. Moore; P. N. Davis; J. F. Sharples; H. O. Werner; O. C. Hicks; J. Gilbert Borton; H. C. Odell; E. V. Hardenburg (American Journal of Potato Research, 1926)

Potato notes - C. Tice; H. G. Zuckerman; W. C. Edmundson; W. L. Floyd; G. W. Waller; A. J. Johnston; E. P. Miller; E. A. Stokdyk; G. L. Tiebout; H. C. Moore; Walter M. Peacock; Andrew Schnetzler; et al. (American Journal of Potato Research, 1925)

Potato notes - C. Tice; A. J. Johnston; E. P. Miller; E. A. Stokdyk; J. W. Weston; A. G. Tolass; J. Norton Woodruff; Ellwood Douglass; Wm. H. Martin; W. S. Blair; N. W. Glines; J. Tucker; et al. (American Journal of Potato Research, 1924)

Potato notes - C. W. Tice; J. T. Rosa; A. E. Wilkinson; E. A. Stokdyk; E. L. Newdick; Verdal T. Maxwell; C. F. Clark; W. Stuart; Charles A. Thompson; J. Gilbert Borton; Ellwood Douglass; Orley G. Bowen; et al. (American Journal of Potato Research, 1924)

Potato notes - J. T. Rosa; E. A. Stokdyk; H. J. Wheeler; J. F. Hockey; H. O. Werner; W. H. Martin; O. G. Bowen; J. Gilbert Barton; Wm. B. Duryee; J. C. Crissey; A. H. C. Odell; C. R. Inglee; et al. (American Journal of Potato Research, 1924)